Enhanced perovskite materials for photovoltaic devices
Patent Information
- Application Number
- CN202411277214.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-28
- Filing Date
- 2019-11-08
- Publication Date
- 2024-12-13
AI Technical Summary
Existing perovskite materials for photovoltaic devices are prone to degradation due to environmental factors such as temperature, humidity, and oxidation, which affects their durability and efficiency.
Incorporation of bulky organic cations near the surface or grain boundaries of the perovskite lattice, with specific cations like 1-butylammonium, benzylammonium, and 1,4-diammoniumbutane, and a controlled annealing process to form perovskite materials with cubic structures, enhancing stability and efficiency.
The proposed perovskite materials exhibit improved durability and efficiency by reducing degradation, with enhanced performance characteristics such as increased open-circuit voltage and power conversion efficiency.
Smart Images

Figure CN119136633A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application 201980087628.0, filed on November 8, 2019, entitled “Enhanced perovskite materials for photovoltaic devices”.
[0002] This application claims priority to U.S. Provisional Patent Application No. 62 / 770,313, filed on November 21, 2018, entitled “Enhanced Perovskite Materials for Photovoltaic Devices.” Background Art
[0003] The use of photovoltaic elements (PV) to generate electrical energy from solar energy or radiation can provide many benefits, including, for example, power supply, low or zero emissions, grid-independent power generation, durable physical structure (no moving parts), stable and reliable systems, modular construction, relatively quick installation, safe to manufacture and use, and good public opinion and acceptance for use.
[0004] PVs may incorporate layers of perovskite materials as photoactive layers that generate electrical energy when exposed to light. Some photoactive layers may degrade due to environmental factors, including temperature, humidity, and oxidation. Therefore, improving the durability and efficiency of perovskite materials is desirable.
[0005] The features and advantages of the present disclosure are obvious to those skilled in the art, and those skilled in the art may make many changes, which are within the spirit of the present invention. SUMMARY OF THE INVENTION
[0007] To address the above-mentioned problems with existing solutions, enhanced perovskite materials and methods of forming such materials are disclosed.
[0008] According to some embodiments, the perovskite material has the formula C x M y X z The perovskite lattice of wherein x, y and z are real numbers. The bulky organic cation is located near the surface or grain boundary of the perovskite lattice. C includes one or more cations selected from Group 1 metals, Group 2 metals, ammonium, formamidinium, guanidinium and ethylenetetramine. M includes one or more metals each selected from Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr and combinations thereof. X includes one or more anions each selected from halogen ions, pseudohalogen ions, chalcogen ions (tellurium ions, oxygen ions, sulfide ions and selenium ions) and combinations thereof.
[0009] In certain embodiments, the tail group of at least one bulky organic cation is not chemically attached to the surface or grain boundaries of the perovskite material.
[0010] In certain embodiments, the bulky organic cation is located within the perovskite material lattice less than 50 nm from a surface or grain boundary of the perovskite material lattice.
[0011] In a particular embodiment, the bulky organic cation is selected from n-butylammonium; benzylammonium; butane-1,4-diammonium; pentylammonium; hexylammonium; poly(vinylammonium); phenethylammonium; 3-phenyl-1-propylammonium; 4-phenyl-1-butylammonium; 1,3-dimethylbutylammonium; 3,3-dimethylbutylammonium and 1-octylammonium and combinations thereof.
[0012] In certain embodiments, the bulky organic cation comprises 1-butylammonium.
[0013] In certain embodiments, the bulky organic cation comprises 1-hexylammonium.
[0014] In certain embodiments, the bulky organic cation comprises 1-octylammonium.
[0015] In certain embodiments, the bulky organic cation comprises benzyl ammonium.
[0016] In certain embodiments, the perovskite material lattice has a cubic structure.
[0017] According to some embodiments, the perovskite material includes a formamidinium lead iodide perovskite material. The benzyl ammonium cations are located near the surface or grain boundaries of the formamidinium lead iodide perovskite material.
[0018] In certain embodiments, at least one benzyl group of the benzyl ammonium cation is not chemically attached to a grain boundary or a surface of the formamidinium lead iodide perovskite material.
[0019] In certain embodiments, the benzyl ammonium cation is located within the formamidinium lead perovskite material less than 50 nm from a surface or grain boundary of the formamidinium lead perovskite material.
[0020] In certain embodiments, the formamidinium lead iodide perovskite material has a cubic crystal structure.
[0021] According to some embodiments, a method of depositing a perovskite material includes depositing a lead salt precursor onto a substrate to form a lead salt film, depositing a bulk organic cation solution onto the lead salt film, depositing a second salt precursor onto the lead salt film to form a perovskite precursor film, and annealing the substrate to form a perovskite material.
[0022] In certain embodiments, the bulk organic cation solution comprises a bulk organic cation selected from the group consisting of n-butylammonium; benzylammonium; butane-1,4-diammonium; pentylammonium; hexylammonium; poly(vinylammonium); phenethylammonium; 3-phenyl-1-propylammonium; 4-phenyl-1-butylammonium; 1,3-dimethylbutylammonium; 3,3-dimethylbutylammonium, 1-octylammonium, ammonium functionalized perylene, and combinations thereof.
[0023] In certain embodiments, the bulk organic cation solution comprises 1-butylammonium.
[0024] In certain embodiments, the bulk organic cation solution comprises benzyl ammonium.
[0025] In certain embodiments, the bulk organic cation solution has a bulk organic cation concentration of 0.01 to 0.1M.
[0026] In certain embodiments, the bulk organic cation solution has a bulk organic cation concentration of 0.03 to 0.05M.
[0027] In certain embodiments, the lead salt precursor, the second salt precursor, and the bulk cationic solution are deposited by spin coating, slot printing, sputtering, PE-CVD, thermal evaporation, or spraying.
[0028] In certain embodiments, the lead salt precursor comprises one or more lead salts selected from lead (II) iodide, lead (II) thiocyanate, lead (II) chloride, lead (II) bromide, and combinations thereof.
[0029] In certain embodiments, the lead salt precursor comprises lead (II) iodide.
[0030] In certain embodiments, the second salt precursor comprises formamidinium iodide, formamidinium thiocyanate, or guanidinium thiocyanate.
[0031] In certain embodiments, the second salt precursor comprises formamidinium iodide.
[0032] In certain embodiments, the lead salt precursor comprises one or more solvents selected from the group consisting of N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof.
[0033] In certain embodiments, the lead salt precursor comprises one or more additives selected from the group consisting of amino acids, 5-aminopentanoic acid hydroiodide, 1,8-diiodooctane, 1,8-dithiooctane, formamidinium halides, acetic acid, trifluoroacetic acid, methylammonium halides, water, and combinations thereof.
[0034] In a particular embodiment, the lead salt precursor comprises a 90:10 molar ratio of PbI2 and PbCl2 dissolved in anhydrous DMF.
[0035] In a particular embodiment, the annealing is performed in an atmosphere selected from the group consisting of ambient air, a controlled humidity environment, pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, and combinations thereof.
[0036] In a specific embodiment, the annealing is performed at a temperature greater than or equal to 50°C and less than or equal to 300°C.
[0037] In a specific embodiment, the annealing in a controlled humidity environment is performed at a temperature greater than or equal to 0 gH2O / m 3 Air and less than or equal to 20g H2O / m 3 The absolute humidity of the air is measured under the absolute humidity.
[0038] In a specific embodiment, the annealing in a controlled humidity environment is performed at about 4 to 7 gH2O / m 3 The absolute humidity of the air.
[0039] According to some embodiments, the perovskite material comprises a x M y X z The perovskite lattice of wherein x, y and z are real numbers. The 1,4-diammonium butane cation is disposed in the perovskite lattice or at the surface of the perovskite lattice. C comprises one or more cations selected from Group 1 metals, Group 2 metals, ammonium, formamidinium, guanidinium and ethylenetetramine, M comprises one or more metals, each of which is selected from Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr and combinations thereof, and X comprises one or more anions, each of which is selected from halogen ions, pseudohalogen ions, chalcogen ions and combinations thereof.
[0040] In certain embodiments, the 1,4-diammoniumbutane cation has a concentration of 1 mol % to 20 mol % in the perovskite material.
[0041] In certain embodiments, the 1,4-diammoniumbutane cation has a concentration of 1 mol % to 5 mol % in the perovskite material.
[0042] In certain embodiments, the 1,4-diammoniumbutane cation has a concentration of about 5 mol % in the perovskite material.
[0043] In certain embodiments, C comprises formamidinium, M comprises lead, and X comprises iodide.
[0044] In certain embodiments, the perovskite material lattice has a cubic structure.
[0045] In certain embodiments, the ammonium group of the 1,4-diammoniumbutane cation replaces the formamidinium ion in the perovskite lattice.
[0046] According to some embodiments, the perovskite material includes a formamidinium lead iodide perovskite material and a 1,4-diammoniumbutane cation disposed inside or at a surface of the formamidinium lead iodide perovskite material.
[0047] In certain embodiments, the ammonium group of the 1,4-diammoniumbutane cation replaces the formamidinium ion in the perovskite lattice.
[0048] In certain embodiments, the 1,4-diammoniumbutane cation has a concentration of 1 mol % to 20 mol % in the perovskite material.
[0049] In certain embodiments, the 1,4-diammoniumbutane cation has a concentration of 1 mol % to 5 mol % in the perovskite material.
[0050] In certain embodiments, the 1,4-diammoniumbutane cation has a concentration of about 5 mol % in the perovskite material.
[0051] In certain embodiments, the formamidinium lead iodide perovskite material has a cubic crystal structure.
[0052] According to some embodiments, a method of depositing a perovskite material includes depositing a lead salt precursor onto a substrate to form a lead salt film. The lead salt precursor comprises a lead salt and a 1,4-diammonium butane salt. Then, a second salt precursor may be deposited onto the lead salt film to form a perovskite precursor film. Then, the substrate and the perovskite precursor film may be annealed to form a perovskite material.
[0053] In certain embodiments, the lead salt precursor has a 1,4-diammoniumbutane concentration of 1 mol % to 20 mol %.
[0054] In certain embodiments, the lead salt precursor has a 1,4-diammoniumbutane concentration of 1 mol % to 5 mol %.
[0055] In certain embodiments, the lead salt precursor has a 1,4-diammoniumbutane concentration of about 5 mole percent.
[0056] In certain embodiments, the lead salt precursor comprises one or more lead salts selected from lead (II) iodide, lead (II) thiocyanate, lead (II) chloride, lead (II) bromide, and combinations thereof.
[0057] In certain embodiments, the lead salt precursor comprises lead (II) iodide.
[0058] In certain embodiments, the second salt precursor comprises a salt selected from the group consisting of formamidinium iodide, formamidinium thiocyanate, guanidinium thiocyanate, and combinations thereof.
[0059] In certain embodiments, the second salt precursor comprises formamidinium iodide.
[0060] In certain embodiments, the lead salt precursor comprises one or more solvents selected from the group consisting of N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide, methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof.
[0061] In certain embodiments, the lead salt precursor comprises one or more additives selected from the group consisting of amino acids, 5-aminopentanoic acid hydroiodide, 1,8-diiodooctane, 1,8-dithiooctane, formamidinium halides, acetic acid, trifluoroacetic acid, methylammonium halides, water, and combinations thereof.
[0062] In a particular embodiment, the lead salt precursor comprises a 90:10 molar ratio of PbI2 and PbCl2 dissolved in anhydrous dimethylformamide.
[0063] In a particular embodiment, the annealing is performed in an atmosphere selected from the group consisting of ambient air, a controlled humidity environment, pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, and combinations thereof.
[0064] In a specific embodiment, the annealing is performed at a temperature greater than or equal to 50°C and less than or equal to 300°C.
[0065] In a specific embodiment, the annealing in a controlled humidity environment is performed at a temperature greater than or equal to 0 gH2O / m 3 Air and less than or equal to 20g H2O / m 3 The absolute humidity of the air is measured under the absolute humidity.
[0066] In a specific embodiment, the annealing in a controlled humidity environment is performed at about 4 to 7 gH2O / m 3 The absolute humidity of the air.
[0067] According to some embodiments, the method of depositing a perovskite material includes depositing a lead salt precursor onto a substrate to form a lead salt film. Next, a 1,4-diammonium butane salt precursor is deposited onto the lead salt film. Next, a third salt precursor may be deposited onto the lead salt film to form a perovskite precursor film. Next, the substrate and the perovskite precursor film may be annealed to form a perovskite material.
[0068] In certain embodiments, the lead salt precursor has a 1,4-diammoniumbutane concentration of 1 mol % to 5 mol %.
[0069] In certain embodiments, the lead salt precursor comprises lead (II) iodide and the third salt precursor comprises formamidinium iodide.
[0070] In a specific embodiment, the lead salt precursor comprises a 90:10 molar ratio of PbI2 to PbCl2 dissolved in anhydrous dimethylformamide and comprises up to 10 mole % of cesium. Annealing is performed at a temperature greater than or equal to 50°C and less than or equal to 300°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 is a schematic diagram of a typical photovoltaic cell including an active layer according to some embodiments of the present disclosure.
[0073] Figure 2 is a stylized diagram showing components of an exemplary PV device according to some embodiments of the present disclosure.
[0074] Figure 3 is a stylized diagram showing components of an exemplary device according to some embodiments of the present disclosure.
[0075] Figure 4 is a stylized diagram showing components of an exemplary device according to some embodiments of the present disclosure.
[0076] Figure 5 is a stylized diagram showing a diagram of a Ruddlesden-Popper perovskite.
[0077] Figure 6 is a stylized diagram showing a representation of a perovskite material with the addition of alkylammonium cations according to some embodiments of the present disclosure.
[0078] Figure 7 is a stylized diagram showing a representation of a perovskite material having a 1-butylammonium surface layer according to some embodiments of the present disclosure.
[0079] Figure 8 is a stylized diagram showing a representation of a perovskite material having a surface layer of multiple bulky organic cations according to some embodiments of the present disclosure.
[0080] Fig. 8A is a stylized diagram showing a representation of a perovskite material having a surface layer of multiple bulky organic cations according to some embodiments of the present disclosure.
[0081] Fig. 9is a diagram comparing images taken of perovskite materials with and without a 1-butylammonium ("BAI") surface coating according to some embodiments of the present disclosure.
[0082] Fig.10 is a stylized diagram showing a graphical comparison of images taken of perovskite materials with and without a 1-butylammonium ("BAI") surface coating according to some embodiments of the present disclosure.
[0083] Fig.11A -D shows various perylene monoimides and diimides that may be applied to the surface of the perovskite material according to some embodiments of the present disclosure.
[0084] Fig.12 is a stylized diagram showing a representation of a perovskite material with the addition of perylene monoimide ammonium cations according to some embodiments of the present disclosure.
[0085] Fig.13 is a stylized diagram showing a representation of 1,4-diaminiumbutane incorporated into the crystal lattice of a formamidinium lead iodide perovskite material according to some embodiments of the present disclosure.
[0086] Fig.14 is a graphical representation of x-ray diffraction peaks (XRD) of perovskites with various concentrations of 1,4-diammoniumbutane according to some embodiments of the present disclosure.
[0087] Fig.15 Images of perovskite material samples with various concentrations of 1,4-diammoniumbutane over time are provided according to some embodiments of the present disclosure.
[0088] Fig.16 A schematic representation of a polyammonium alkyl cation according to some embodiments of the present disclosure is provided.
[0089] Fig.16A is a stylized diagram showing a representation of 1,8-diaminoctane incorporated into a formamidinium lead iodide perovskite material lattice, according to some embodiments of the present disclosure.
[0090] Fig. 16B is a stylized diagram showing a representation of bis(4-aminobutyl)-ammonium incorporated into a formamidinium lead iodide perovskite material lattice, according to some embodiments of the present disclosure.
[0091] Fig. 16C is a stylized diagram showing a representation of tris(4-aminobutyl)-ammonium incorporated into a formamidinium lead iodide perovskite material lattice, according to some embodiments of the present disclosure.
[0092] Figure 17-28 Illustrations of the structures of certain organic molecules according to some embodiments of the present disclosure are provided.
[0093] Fig.29 An x-ray diffraction pattern of a perovskite material according to some embodiments of the present disclosure is shown.
[0094] Fig.30 A stylized illustration of the thickness of an inorganic metal halide sublattice of a perovskite material according to some embodiments of the present disclosure is provided.
[0095] Fig.31 Optical and photoluminescence images of perovskite material photovoltaic devices according to some embodiments of the present disclosure are shown.
[0096] Fig.32 Shown are power output curves of perovskite material photovoltaic devices according to some embodiments of the present disclosure.
[0097] Fig.33 A current-voltage (IV) scan graph of a perovskite material photovoltaic device according to some embodiments of the present disclosure is shown.
[0098] Fig.34 Box plots of open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF), and power conversion efficiency (PCE) of perovskite material photovoltaic devices according to some embodiments of the present disclosure are shown.
[0099] Fig.35 An external quantum efficiency (EQE) curve of a perovskite material photovoltaic device according to some embodiments of the present disclosure is shown.
[0100] Fig.36 Shown is an admittance spectrum graph of a perovskite material photovoltaic device according to some embodiments of the present disclosure.
[0101] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0102] Improvements in various aspects of PV technology that are compatible with organic, inorganic, and / or hybrid PV are expected to further reduce the cost of organic and other PV. For example, some solar cells (such as perovskite PV solar cells) can utilize novel cost-effective and high-stability alternative components, such as nickel oxide interfacial layers. In addition, various solar cells can advantageously include chemical additives and other materials that, among other advantages, can be more cost-effective and durable than currently existing conventional options.
[0103] The present disclosure generally relates to compositions of matter, devices and methods of use of materials in photovoltaic cells that generate electrical energy from solar radiation. More specifically, the present disclosure relates to photoactive and other compositions of matter, and devices, methods of use and formation of such compositions of matter.
[0104] Some or all of the materials according to some embodiments of the present disclosure may also be advantageously used in any organic or other electronic device, some examples of which include but are not limited to: batteries, field effect transistors (FETs), light emitting diodes (LEDs), nonlinear optical devices, memristors, capacitors, rectifiers, and / or rectennas.
[0105] In some embodiments, the present disclosure may provide PV and other similar devices (e.g., batteries, hybrid PV cells, multi-junction PV, FETs, LEDs, x-ray detectors, gamma-ray detectors, photodiodes, CCDs, etc.). Such devices may include improved active materials, interfacial layers (IFLs), and / or one or more perovskite materials in some embodiments. Perovskite materials may be incorporated into various aspects of one or more aspects of PV or other devices. Perovskite materials according to some embodiments may have the general formula CMX3, wherein: C comprises one or more cations (e.g., amines, ammonium, phosphonium, Group 1 metals, Group 2 metals, and / or other cations or quasi-cation compounds); M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X comprises one or more anions. Perovskite materials according to various embodiments are discussed in more detail below.
[0106] Photovoltaic cells and other electronic devices
[0107] Some PV implementation schemes can be found in Figure 1 . An exemplary PV architecture according to some embodiments may be substantially of the form substrate-anode-IFL-active layer-IFL-cathode. The active layer of some embodiments may be photoactive, and / or it may include photoactive materials. Other layers and materials may be used in the unit as is known in the art. Furthermore, it should be noted that the use of the term "active layer" is in no way meant to explicitly or implicitly limit or otherwise define the properties of any other layer - for example, in some embodiments, one or both IFLs may also be active, provided that they may be semiconducting. In particular, with reference to Figure 1 , depicts a stylized generic PV cell 1000 showing the highly interfacial nature of some layers in the PV. The PV 1000 represents a generic architecture applicable to several PV devices, such as perovskite material PV embodiments. The PV cell 1000 includes a transparent substrate layer 1010, which may be glass (or a similar material transparent to solar radiation), that allows solar radiation to pass through the layer. The transparent layer of some embodiments may also be referred to as a superstrate or substrate (e.g., with a substrate having a substantially transparent surface). Figure 2The photoactive layer 1040 may be the same as the substrate layer 3901 of the photoactive layer 1040), and it may include any one or more of a variety of rigid or flexible materials, such as glass, polyethylene, polypropylene, polycarbonate, polyimide, PMMA, PET, PEN, Kapton, or quartz. Typically, the term substrate is used to refer to the material on which the device is deposited during the manufacturing process. The photoactive layer 1040 may be composed of an electron donor or p-type material, and / or an electron acceptor or n-type material, and / or an ambipolar semiconductor exhibiting p-type and n-type material properties, and / or an intrinsic semiconductor exhibiting n-type or p-type properties. In some embodiments, the photoactive layer 1040 may be a perovskite material as described herein. The active layer, or as Figure 1 As shown in , the photoactive layer 1040 is sandwiched between two conductive electrode layers 1020 and 1060. Figure 1 In the embodiment, the electrode layer 1020 can be a transparent conductor, such as tin-doped indium oxide (ITO material) or other materials described herein. In other embodiments, the second substrate 1070 and the second electrode 1060 can be transparent. As previously mentioned, the active layer of some embodiments is not necessarily photoactive, although in Figure 1 In the device shown in FIG. 1 , it is photoactive. Electrode layer 1060 may be an aluminum material or other metal, or other conductive material, such as carbon. Other materials known in the art may be used. Unit 1010 also includes Figure 1 In the example of , an interfacial layer (IFL) 1030 is shown. The IFL can assist in charge separation. In other embodiments, the IFL 1030 can include multiple layers of IFLs, which are discussed in more detail below. There can also be an IFL 1050 adjacent to the electrode 1060. In some embodiments, the IFL 1050 adjacent to the electrode 1060 can also or alternatively include multiple layers of IFLs (also discussed in more detail below). The IFL according to some embodiments can be semiconducting in nature and can be intrinsic, bipolar, p-type, or n-type, or it can be dielectric in nature. In some embodiments, the IFL on the cathode side of the device (e.g. Figure 1 The IFL 1050 shown in FIG. 1050 may be p-type. The IFL on the anode side of the device (eg Figure 1 1030) can be n-type. However, in other embodiments, the cathode side IFL can be n-type and the anode side IFL can be p-type. The cell 1010 can be connected to electrical leads and discharge elements such as batteries, motors, capacitors, power grids, or any other electrical loads via electrodes 1060 and 1020.
[0108] Various embodiments of the present disclosure provide improved materials and / or designs in various aspects of solar cells and other devices, including, inter alia, active materials (including hole transport and / or electron transport layers), interfacial layers, and overall device design.
[0109] Interface layer
[0110] In some embodiments, the present disclosure provides advantageous materials and designs for one or more interface layers in a PV, including a thin coating IFL.The thin coating IFL may be used for one or more IFLs of a PV according to various embodiments discussed herein.
[0111] According to various embodiments, the device may optionally include an interfacial layer between any two other layers and / or materials, although the device need not contain any interfacial layer. For example, a perovskite material device may contain zero, one, two, three, four or more interfacial layers (e.g., Figure 2An exemplary device of the invention comprises five interfacial layers 3903, 3905, 3907, 3909 and 3911). An interfacial layer may comprise any material suitable for enhancing charge transport and / or collection between two layers or materials; it may also help prevent or reduce the likelihood of charge recombination once charge has been transported from one of the materials adjacent to the interfacial layer. The interfacial layer may additionally physically and electrically homogenize its substrate to produce changes in substrate roughness, dielectric constant, adhesion, creation or quenching of defects (e.g., charge traps, surface states). Suitable interface materials may include any one or more of the following: Ag; Al; Au; B; Bi; Ca; Cd; Ce; Co; Cu; Fe; Ga; Ge; H; In; Mg; Mn; Mo; Nb; Ni; Pt; Sb; Sc; Si; Sn; Ta; Ti; V; W; Y; Zn; Zr; carbides of any of the foregoing metals (e.g., SiC, Fe3C, WC, VC, MoC, NbC); silicides of any of the foregoing metals (e.g., Mg2Si, SrS i2, Sn2Si); oxides of any of the foregoing metals (e.g., aluminum oxide, silicon dioxide, titanium dioxide, SnO2, ZnO, NiO, ZrO2, HfO2), including transparent conductive oxides ("TCO") such as indium tin oxide, aluminum-doped zinc oxide (AZO), cadmium oxide (CdO), and fluorine-doped tin oxide (FTO); sulfides of any of the foregoing metals (e.g., CdS, MoS2, SnS2); nitrides of any of the foregoing metals (e.g., GaN, Mg3N2, T iN, BN, Si3N4); selenides of any of the foregoing metals (e.g., CdSe, FeS2, ZnSe); tellurides of any of the foregoing metals (e.g., CdTe, TiTe2, ZnTe); phosphides of any of the foregoing metals (e.g., InP, GaP, GaInP); arsenides of any of the foregoing metals (e.g., CoAs3, GaAs, InGaAs, NiAs); antimonides of any of the foregoing metals (e.g., AlSb, GaSb, InSb); Halides (e.g., CuCl, CuI, BiI3); pseudohalides of any of the foregoing metals (e.g., CuSCN, AuCN, Fe(SCN)2); carbonates of any of the foregoing metals (e.g., CaCO3, Ce2(CO3)3); functionalized or non-functionalized alkylsilyl groups; graphite; graphene; fullerenes; carbon nanotubes; any mesoporous material and / or interface material discussed elsewhere herein; and combinations thereof (including, in some embodiments, double, triple, or multiple layers of combined materials). In some embodiments, the interfacial layer may include a perovskite material. In addition, the interfacial layer may include a doped embodiment of any of the interfacial materials mentioned herein (e.g., Y-doped ZnO, N-doped single-walled carbon nanotubes).The interface layer may also contain a compound having three of the above materials (e.g., CuTiO3, Zn2SnO4) or a compound having four of the above materials (e.g., CoNiZnO). The compounds listed above may be present in planar, mesoporous or otherwise nanostructured forms (e.g., rods, balls, flowers, pyramids) or aerogel structures.
[0112] First, as mentioned above, one or more IFLs (e.g. Figure 1 One or both of the IFL 1030 and 1050 shown in (a) can contain the photoactive organic compound of the present disclosure in the form of a self-assembled monolayer (SAM) or in the form of a thin film. When the photoactive organic compound of the present disclosure is applied in the form of a SAM, it can contain a binding group, which can be covalently or otherwise bonded to the surface of the anode and / or cathode through the binding group. The binding group of some embodiments can include any one or more of COOH, SiX3 (wherein X can be any part suitable for forming a ternary silicon compound such as Si(OR)3 and SiCl3), SO3, PO4H, OH, CH2X (wherein X can contain a halogen of the 17th group) and O. The binding group can be covalently or otherwise bonded to an electron-withdrawing part, an electron donor part and / or a core part. The binding group can be attached to the electrode surface (for example, wherein a plurality of photoactive organic compounds are bonded to the anode and / or cathode) in a manner to form a directional, organized layer with a thickness of a single molecule (or in some embodiments, multiple molecules). As described, the SAM can be connected via covalent interactions, but in some embodiments, it can be connected via ionic interactions, hydrogen bonding interactions, and / or dispersion forces (i.e., van der Waals forces). In addition, in certain embodiments, upon exposure to light, the SAM can enter a zwitterionic excited state, thereby generating a highly polarized IFL that can direct charge carriers from the active layer to an electrode (e.g., an anode or cathode). In some embodiments, this enhanced charge carrier injection can be achieved by electronically polarizing the cross-section of the active layer and thereby increasing the charge carrier drift velocity toward its corresponding electrode (e.g., holes to the anode; electrons to the cathode). Molecules for anode applications of some embodiments may include a tunable compound that includes a main electron donor portion bonded to a core portion, which in turn is bonded to an electron withdrawing portion, which in turn is bonded to a binding group. In cathode applications according to some embodiments, the IFL molecule may include a tunable compound that includes an electron-poor portion bonded to a core portion, which in turn is bonded to an electron donor portion, and the electron donor portion in turn is bonded to a binding group. When a photoactive organic compound is used as an IFL according to such embodiments, it may retain photoactive properties, although in some embodiments it need not be photoactive.
[0113] Metal oxides may be used for the thin film IFL of some embodiments, and may include semiconductor metal oxides such as NiO, SnO2, WO3, V2O5, or MoO3. Embodiments in which the second (e.g., n-type) active material comprises TiO2 coated with a thin coating IFL containing Al2O3 may be formed, for example, with a precursor material such as Al(NO3)3·xH2O or any other material suitable for depositing Al2O3 onto TiO2, followed by thermal annealing and dye coating. In an exemplary embodiment in which a MoO3 coating is used, the coating may be formed with a precursor material such as Na2Mo4·2H2O; while a V2O5 coating according to some embodiments may be formed with a precursor material such as NaVO3; and a WO3 coating according to some embodiments may be formed with a precursor material such as NaWO4·H2O. The concentration of the precursor material (e.g., Al(NO3)3·xH2O) may affect the final film thickness (here Al2O3) deposited on TiO2 or other active material. Therefore, varying the concentration of the precursor material may be a method by which the final film thickness is controlled. For example, greater film thickness may result from greater concentration of precursor material. In PV devices comprising metal oxide coatings, greater film thickness may not necessarily result in greater PCE. Thus, the method of some embodiments may include coating a TiO2 (or other mesoporous) layer with a precursor material concentration of about 0.5 to 10.0 mM; other embodiments may include coating the layer with a precursor material concentration of about 2.0 to 6.0 mM; or in other embodiments, about 2.5 to 5.5 mM.
[0114] Furthermore, although referred to herein as Al2O3 and / or alumina, it should be noted that various ratios of aluminum to oxygen may be employed when forming alumina. Thus, although some embodiments discussed herein are described with reference to Al2O3, such descriptions are not intended to limit the required ratios of aluminum to oxygen. Rather, embodiments may include any one or more aluminum-oxide compounds, each having a ratio according to Al2O3. x O y , wherein x can be any value from about 1 to 100, integer or non-integer. In some embodiments, x can be from about 1 to 3 (and again not necessarily an integer). Likewise, y can be any value from 0.1 to 100, integer or non-integer. In some embodiments, y can be from 2 to 4 (and again not necessarily an integer). In addition, Al x O y Various crystalline forms of alumina may be present in various embodiments, such as alpha, gamma, and / or amorphous forms of alumina.
[0115] Likewise, although referred to herein as NiO, MoO3, WO3, and V2O5, such compounds may alternatively or additionally be represented as Ni x Oy 、Mo x O y , W x O y and V x O y About Mo x O y and W x O y In each of , x can be any value from about 0.5 to 100, integer or non-integer; in some embodiments, it can be from about 0.5 to 1.5. Similarly, y can be any value from about 1 to 100, integer or non-integer. In some embodiments, y can be any value from about 1 to 4. x O y , x can be any value from about 0.5 to 100, integer or non-integer; in some embodiments, it can be from about 0.5 to 1.5. Similarly, y can be any value from about 1 to 100, integer or non-integer; in certain embodiments, it can be an integer or non-integer value from about 1 to 10. In some embodiments, the values of x and y can be non-stoichiometric.
[0116] In some embodiments, the IFL may comprise a titanate. Titanates according to some embodiments may have the general formula M'TiO3, wherein M' comprises any 2+ cation. In some embodiments, M' may comprise a cationic form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single species of titanate, and in other embodiments, the IFL may comprise two or more different species of titanates. In one embodiment, the titanate has the formula SrTiO3. In another embodiment, the titanate may have the formula BaTiO3. In yet another embodiment, the titanate may have the formula CaTiO3.
[0117] By way of explanation, and without implying any limitation, titanates have a perovskite crystalline structure and strongly seed the growth conversion process of the perovskite materials (e.g., methylammonium lead iodide (MAPbI3) and formamidinium lead iodide (FAPbI3). Titanates also typically meet other IFL requirements, such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0118] In other embodiments, the IFL may comprise a zirconate. Zirconates according to some embodiments may have the general formula M'ZrO3, wherein M' comprises any 2+ cation. In some embodiments, M' may comprise a cationic form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single species of zirconate, and in other embodiments, the IFL may comprise two or more different species of zirconates. In one embodiment, the titanate has the formula SrZrO3. In another embodiment, the titanate may have the formula BaZrO3. In yet another embodiment, the titanate may have the formula CaZrO3.
[0119] By way of explanation, and without implying any limitation, zirconates have a perovskite crystal structure and strongly seed the perovskite material (e.g., MAPbI3, FAPbI3) growth conversion process. Zirconates also typically meet other IFL requirements such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0120] In other embodiments, the IFL may comprise a stannate. The stannate according to some embodiments may have the general formula M'SnO3 or M'2SnO4, wherein M' comprises any 2+ cation. In some embodiments, M' may comprise a cationic form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn or Pb. In some embodiments, the IFL may comprise a single species of stannate, and in other embodiments, the IFL may comprise two or more different species of stannate. In one embodiment, the stannate has the formula SrSnO3. In another embodiment, the stannate may have the formula BaSnO3. In yet another embodiment, the stannate may have the formula CaSnO3.
[0121] By way of explanation, and without implying any limitation, stannates have a perovskite crystalline structure and strongly seed the perovskite material (e.g., MAPbI3, FAPbI3) growth conversion process. Stannates also typically meet other IFL requirements such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0122] In other embodiments, the IFL may comprise a plumbate. The plumbate according to some embodiments may have the general formula M'PbO3, wherein M' comprises any 2+ cation. In some embodiments, M' may comprise a cationic form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single species of plumbate, and in other embodiments, the IFL may comprise two or more different species of plumbates. In one embodiment, the plumbate has the formula SrPbO3. In another embodiment, the plumbate may have the formula BaPbO3. In yet another embodiment, the plumbate may have the formula CaPbO3. In yet another embodiment, the plumbate may have the formula Pb II Pb IV O3.
[0123] By way of explanation, and without implying any limitation, plumbates have a perovskite crystalline structure and strongly seed the perovskite material (e.g., MAPbI3, FAPbI3) growth conversion process. Plumbates also typically meet other IFL requirements, such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0124] In addition, in other embodiments, IFL can be in the general formula M'[ Zr x Ti 1-x ] O 3 comprises a combination of zirconate and titanate, wherein x is greater than 0 but less than 1, and M' comprises any 2+ cation. In some embodiments, M' may comprise a cationic form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single species of zirconate, and in other embodiments, the IFL may comprise two or more different species of zirconate. In one embodiment, the zirconate / titanate combination has the formula Pb [ Zr x Ti 1-x ] O 3. In another embodiment, the zirconate / titanate combination has the formula Pb [ Zr 0.52 Ti 0.48 ] O 3.
[0125] By way of explanation, and without implying any limitation, zirconate / titanate combinations have a perovskite crystal structure and strongly seed the perovskite material (e.g., MAPbI3, FAPbI3) growth conversion process. Zirconate / titanate combinations also typically meet other IFL requirements, such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0126] In other embodiments, the IFL may comprise a niobate. Niobates according to some embodiments may have the general formula M'NbO3, wherein: M' comprises any 1+ cation. In some embodiments, M' may comprise a cationic form of Li, Na, K, Rb, Cs, Cu, Ag, Au, Tl, ammonium, or H. In some embodiments, the IFL may comprise a single species of niobate, and in other embodiments, the IFL may comprise two or more different species of niobates. In one embodiment, the niobate has the formula LiNbO3. In another embodiment, the niobate may have the formula NaNbO3. In yet another embodiment, the niobate may have the formula AgNbO3.
[0127] By way of explanation, and without implying any limitation, niobates generally meet IFL requirements such as piezoelectric behavior, nonlinear optical susceptibility, photoelasticity, ferroelectric behavior, Pockels effect, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0128] In one embodiment, a perovskite material device can be prepared by casting PbI2 onto an ITO substrate coated with SrTiO3. The PbI2 can be converted to MAPbI3 by an impregnation process. The process is described in more detail below. The resulting conversion of PbI2 to MAPbI3 is more complete (as observed by spectroscopy) than when preparing a substrate without SrTiO3.
[0129] Any interface material discussed herein may further comprise a doping composition. In order to change the properties (e.g., electrical, optical, mechanical) of the interface material, a stoichiometric or non-stoichiometric material may be doped with one or more elements (e.g., Na, Y, Mg, N, P) in an amount as small as 1 ppb to 50 mol%. Some examples of interface materials include: NiO, TiO2, SrTiO3, Al2O3, ZrO2, WO3, V2O5, MO3, ZnO, graphene, and carbon black. Examples of dopants that may be used for these interface materials include: Li, Na, Be, Mg, Ca, Sr, Ba, Sc, Y, Nb, Ti, Fe, Co, Ni, Cu, Ga, Sn, In, B, N, P, C, S, As, halides, pseudohalides (e.g., cyanides, cyanates, isocyanates, fulminates, thiocyanates, isothiocyanates, azides, tetracarbonylcobaltates, carbamoyl dicyanomethanes, dicyanonitrosomethanes, dicyanamides, and tricyanomethanes) and Al in any oxidation state thereof. The reference to doped interface materials herein is not intended to limit the ratio of the component elements in the interface material compound.
[0130] In some embodiments, multiple IFLs made of different materials can be arranged adjacent to each other to form a composite IFL. This configuration can involve two different IFLs, three different IFLs, or even a larger number of different IFLs. The resulting multi-layer IFL or composite IFL can be used to replace a single material IFL. For example, a composite IFL can be used Figure 2 3903, IFL 3905, IFL 3907, IFL 3909, or IFL 3911. Although a composite IFL is different from a single material IFL, the assembly of a perovskite material PV cell with multiple layers of IFLs is not significantly different from the assembly of a perovskite material PV cell with only a single material IFL.
[0131] In general, the composite IFL can be made of any material discussed herein as being suitable for an IFL. In one embodiment, the IFL comprises a layer of Al2O3 and a layer of ZnO or M:ZnO (doped ZnO, such as Be:ZnO, Mg:ZnO, Ca:ZnO, Sr:ZnO, Ba:ZnO, Sc:ZnO, Y:ZnO, Nb:ZnO). In one embodiment, the IFL comprises a layer of ZrO2 and a layer of ZnO or M:ZnO. In certain embodiments, the IFL comprises multiple layers. In some embodiments, the multilayer IFL typically has a conductor layer, a dielectric layer, and a semiconductor layer. In certain embodiments, these layers can be repeated, such as a conductor layer, a dielectric layer, a semiconductor layer, a dielectric layer, and a semiconductor layer. Examples of multilayer IFLs include an IFL having an ITO layer, an Al2O3 layer, a ZnO layer, and a second Al2O3 layer; an IFL having an ITO layer, an Al2O3 layer, a ZnO layer, a second Al2O3 layer, and a second ZnO layer; an IFL having an ITO layer, an Al2O3 layer, a ZnO layer, a second Al2O3 layer, a second ZnO layer, and a third Al2O3 layer; and an IFL having as many layers as necessary to achieve the desired performance characteristics. As previously mentioned, reference to a specific stoichiometric ratio is not intended to limit the ratios of the component elements in the IFL layer according to various embodiments.
[0132] Arranging two or more adjacent IFLs as a composite IFL in a perovskite material PV cell can outperform a single IFL, where properties from each IFL material can be utilized in a single IFL. For example, in an architecture with an ITO layer, an Al2O3 layer, and a ZnO layer (where ITO is a conductive electrode, Al2O3 is a dielectric material, and ZnO is an n-type semiconductor), ZnO acts as an electron acceptor that fully exhibits electron transport properties (e.g., mobility). In addition, Al2O3 is a physically strong material that adheres well to ITO, homogenizes the surface by covering surface defects (e.g., charge traps), and improves device diode characteristics by suppressing dark current.
[0133] Furthermore, some perovskite PV cells may include so-called "cascaded" PV cells having more than one perovskite photoactive layer. Figure 2 The photoactive materials 3908 and 3906 can both be perovskite materials. In such a cascaded PV cell, the interface layer (e.g. Figure 2 The IFL 3907) may comprise a multilayer or composite IFL. In some embodiments, the layer sandwiched between two photoactive layers of a tandem PV device may include an electrode layer.
[0134] The tandem PV device may include the following layers, listed in order from top to bottom or from bottom to top: a first substrate, a first electrode, a first interface layer, a first perovskite material, a second interface layer, a second electrode, a third interface layer, a second perovskite material, a fourth interface layer, and a third electrode. In some embodiments, the first and third interface layers may be hole transport interface layers, and the second and fourth interface layers may be electron transport interface layers. In other embodiments, the first and third interface layers may be electron transport interface layers, and the second and fourth interface layers may be hole transport interface layers. In yet another embodiment, the first and fourth interface layers may be hole transport interface layers, and the second and third interface layers may be electron transport interface layers. In other embodiments, the first and fourth interface layers may be electron transport interface layers, and the second and third interface layers may be hole transport interface layers. In a tandem PV device, the first and second perovskite materials may have different band gaps. In some embodiments, the first perovskite material may be formamidinium lead bromide (FAPbBr3), and the second perovskite material may be formamidinium lead iodide (FAPbI3). In other embodiments, the first perovskite material may be methylammonium lead bromide (MAPbBr3) and the second perovskite material may be formamidinium lead iodide (FaPbI3). In other embodiments, the first perovskite material may be methylammonium lead bromide (MAPbBr3) and the second perovskite material may be methylammonium lead iodide (MAPbI3).
[0135] Perovskite materials
[0136] Perovskite materials may be incorporated into one or more aspects of PV or other devices. Perovskite materials according to some embodiments may have the general formula C w M y X z , wherein: C comprises one or more cations (e.g., amines, ammonium, phosphonium, Group 1 metals, Group 2 metals, and / or other cations or quasi-cation compounds); M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); X comprises one or more anions; and w, y, and z represent real numbers from 1 to 20. In some embodiments, C may include one or more organic cations. In some embodiments, each organic cation C may be greater than each metal M, and each anion X may be bonded to both the cation C and the metal M. In certain embodiments, the perovskite material may have the formula CMX3.
[0137] In certain embodiments, C may include ammonium - general formula [NR4] +The organic cation, wherein the R groups can be the same or different groups. Suitable R groups include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne C x H y , wherein x=1-20, y=1-42, cyclic, branched or linear; alkyl halide C x H y X z , x=1-20, y=0-42, z=1-42, X=F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen in the ring (e.g. pyridine, pyrrole, pyrrolidine, piperidine, tetrahydroquinoline); any sulfur-containing group (e.g. sulfoxide, thiol, alkylsulfide); any nitrogen-containing group (nitroxide, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g. boric acid); any organic acid (e.g. acetic acid, propionic acid); and its ester or amide derivatives; any amino acid (e.g. glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammoniopentanoic acid), including α, β, γ and higher derivatives; any silicon-containing group (e.g. siloxane); and any alkoxy or group -OC x H y , where x=0-20, y=1-42.
[0138] In certain embodiments, C may include a carboxamidinium compound of the general formula [R2NCRNR2] + The organic cation, wherein the R groups can be the same or different groups. Suitable R groups include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne C x H y , wherein x=1-20, y=1-42, cyclic, branched or linear; alkyl halide C x H y X z, x=1-20, y=0-42, z=1-42, X=F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen in the ring (e.g. imidazole, benzimidazole, pyrimidine, (pyrrolidinylmethyl)pyrrolidine, triazole); any sulfur-containing group (e.g. sulfoxide, thiol, alkylsulfide); any nitrogen-containing group (nitroxide, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g. boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g. glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammoniopentanoic acid), including α, β, γ and higher derivatives; any silicon-containing group (e.g. siloxane); and any alkoxy group or group -OCxHy, wherein x=0-20, y=1-42.
[0139]
[0140] Formula 1 shows the general formula [R2NCRNR2] as described above. + Formula 2 shows exemplary structures of several formamidinium cations that can be used as cation "C" in perovskite materials.
[0141]
[0142]
[0143] In certain embodiments, C may include a guanidinium, formula [(R2N)2C=NR2] + The organic cation, wherein the R groups can be the same or different groups. Suitable R groups include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne C x H y , wherein x=1-20, y=1-42, cyclic, branched or linear; alkyl halide C x H y X z, x=1-20, y=0-42, z=1-42, X=F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); a cyclic complex containing at least one nitrogen in the ring (e.g. octahydropyrimido[1,2-a]pyrimidine, pyrimido[1,2-a]pyrimidine, hexahydroimidazo[1,2-a]imidazole, hexahydropyrimidin-2-imine); any sulfur-containing group (e.g. sulfoxide, thiol); , alkylthio); any nitrogen-containing group (nitroxide, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammoniopentanoic acid), including α, β, γ and higher derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or group -OC x H y , where x=0-20, y=1-42.
[0144]
[0145] Formula 3 shows a compound having the general formula [(R2N)2C=NR2] as described above. + Formula 4 shows exemplary structures of several guanidinium cations that can be used as the cation "C" in the perovskite material.
[0146]
[0147] In certain embodiments, C may include an ethylenetetramine cation of the general formula [(R2N)2C=C(NR2)2] + The organic cation, wherein the R groups can be the same or different groups. Suitable R groups include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne C x H y , wherein x=1-20, y=1-42, cyclic, branched or linear; alkyl halide C x H y X z, x=1-20, y=0-42, z=1-42, X=F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); a cyclic complex containing at least one nitrogen in the ring (e.g. 2-hexahydropyrimidin-2-ylidenehexahydropyrimidine, octahydropyrazino[2,3-b]pyrazine, pyrazino[2,3-b]pyrazine, quinoxalino[2,3-b]quinoxaline); any sulfur-containing group (e.g. sulfoxide , thiol, alkylthio); any nitrogen-containing group (nitroxide, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammoniopentanoic acid), including α, β, γ and higher derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or group -OC x H y , where x=0-20, y=1-42.
[0148]
[0149] Formula 5 shows the general formula [(R2N)2C=C(NR2)2] as described above. + Formula 6 shows examples of structures of several ethylenetetramine ions that can be used as the cation "C" in the perovskite material.
[0150]
[0151]
[0152] In certain embodiments, C may include an imidazolium cation of the general formula [CRNRCRNRCR] + The aromatic cyclic organic cation of wherein the R groups may be the same or different groups. Suitable R groups may include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne C x H y , wherein x=1-20, y=1-42, cyclic, branched or linear; alkyl halide C x H y X z, x=1-20, y=0-42, z=1-42, X=F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); a cyclic complex containing at least one nitrogen in the ring (e.g. 2-hexahydropyrimidin-2-ylidenehexahydropyrimidine, octahydropyrazino[2,3-b]pyrazine, pyrazino[2,3-b]pyrazine, quinoxalino[2,3-b]quinoxaline); any sulfur-containing group (e.g. sulfoxide , thiol, alkylthio); any nitrogen-containing group (nitroxide, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammoniopentanoic acid), including α, β, γ and higher derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or group -OC x H y , where x=0-20, y=1-42.
[0153]
[0154] In some embodiments, X may include one or more halide ions. In certain embodiments, X may alternatively or additionally include a Group 16 anion. In certain embodiments, a Group 16 anion may be an oxygen ion, a sulfide ion, a selenium ion, or a tellurium ion. In certain embodiments, X may alternatively or additionally include one or more pseudohalides (e.g., cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethanide, dicyanonitrosomethanide, dicyanamide, and tricyanomethanide).
[0155] In one embodiment, the perovskite material may comprise the empirical formula CMX3, wherein: C comprises one or more of the aforementioned cations, Group 1 metals, Group 2 metals, and / or other cations or quasi-cation compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X comprises one or more of the aforementioned anions.
[0156] In another embodiment, the perovskite material may comprise the empirical formula C'M2X6, wherein: C' comprises a cation having a 2+ charge, including one or more of the aforementioned cations, diammonium butane, Group 1 metals, Group 2 metals, and / or other cations or quasi-cation compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X comprises one or more of the aforementioned anions.
[0157] In another embodiment, the perovskite material may comprise the empirical formula C'MX4, wherein: C' comprises a cation having a 2+ charge, including one or more of the aforementioned cations, diammonium butane, Group 1 metals, Group 2 metals, and / or other cations or quasi-cation compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X comprises one or more of the aforementioned anions. In such embodiments, the perovskite material may have a 2D structure.
[0158] In one embodiment, the perovskite material may comprise the empirical formula C3M2X9, wherein: C comprises one or more of the aforementioned cations, Group 1 metals, Group 2 metals, and / or other cations or quasi-cation compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X comprises one or more of the aforementioned anions.
[0159] In one embodiment, the perovskite material may comprise the empirical formula CM2X7, wherein: C comprises one or more of the aforementioned cations, Group 1 metals, Group 2 metals, and / or other cations or quasi-cation compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr n); and X comprises one or more of the aforementioned anions.
[0160] In one embodiment, the perovskite material may comprise the empirical formula C2MX4, wherein: C comprises one or more of the aforementioned cations, Group 1 metals, Group 2 metals, and / or other cations or quasi-cation compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X comprises one or more of the aforementioned anions.
[0161] Perovskite materials can also include mixed ion formulations where C, M or X comprises two or more species, such as Cs 0.1 FA 0.9 Pb(I 0.9 Cl 0.1 )3; Rb 0.1 FA 0.9 Pb(I 0.9 Cl 0.1 )3; Cs 0.1 FA 0.9 PbI3; FAPb 0.5 Sn 0.5 I3;FA 0.83 Cs 0.17 Pb(I 0.6 Br 0.4 )3;FA 0.83 Cs 0.12 R 0.05 Pb(I 0.6 Br 0.4 )3 and FA 0.85 MA 0.15 Pb(I 0.85 Br 0.15 )3.
[0162] Composite perovskite material device design
[0163] In some embodiments, the present disclosure may provide composite designs of PV and other similar devices (e.g., cells, hybrid PV cells, FETs, LEDs, nonlinear optical elements (NLOs), waveguides, etc.) that include one or more perovskite materials. For example, one or more perovskite materials may be used as the first and second active materials of some embodiments (e.g., Figure 3One or both of the active materials 3906a and 3908a). More generally, some embodiments of the present disclosure provide PV or other devices having an active layer comprising one or more perovskite materials. In such embodiments, perovskite materials (i.e., materials including any one or more perovskite materials) can be used in active layers of various architectures. In addition, perovskite materials can be used for the functions of any one or more components of the active layer (e.g., charge transport materials, mesoporous materials, photoactive materials, and / or interface materials, each of which will be discussed in more detail below). In some embodiments, the same perovskite material can be used for a variety of such functions, although in other embodiments, a variety of perovskite materials can be included in the device, but each perovskite material is used for one or more such functions. In certain embodiments, no matter what role the perovskite material can play, it can be prepared and / or present in the device in various states. For example, in some embodiments, it can be substantially solid. A solution or suspension can be coated or otherwise deposited in a device (e.g., on another component of the device, such as a mesoporous, interface, charge transport, photoactive or other layer, and / or on an electrode). In some embodiments, the perovskite material may be formed in situ on a surface of another component of the device (eg, as a thin film solid by vapor deposition).Any other suitable means of forming a layer comprising a perovskite material may be used.
[0164] Typically, a perovskite material device may include a first electrode, a second electrode, and an active layer comprising a perovskite material, the active layer being at least partially disposed between the first and second electrodes. In some embodiments, the first electrode may be one of an anode and a cathode, and the second electrode may be another of an anode and a cathode. The active layer according to certain embodiments may include any one or more active layer components, including any one or more of the following: charge transport material; liquid electrolyte; mesoporous material; photoactive material (e.g., dye, silicon, cadmium telluride, cadmium sulfide, cadmium selenide, copper indium gallium selenide, gallium arsenide, indium germanium phosphide, semiconductor polymer, other photoactive materials); and interface material. Any one or more of these active layer components may include one or more perovskite materials. In some embodiments, some or all of the active layer components may be arranged in full or in part in sublayers. For example, the active layer may include any one or more of the following: an interface layer including an interface material; a mesoporous layer including a mesoporous material; and a charge transport layer including a charge transport material. In addition, the interface layer may be included between any two or more other layers of the active layer according to some embodiments and / or between the active layer component and the electrode. References to layers herein may include the final arrangement (e.g., substantially discrete portions of each material that may be individually defined in a device), and / or references to layers may refer to the arrangement during construction of a device, although materials may be subsequently mixed in each layer. Layers may be discrete in some embodiments and include substantially contiguous materials (e.g., layers may be stylized as shown in FIG. Figure 2 middle).
[0165] In some embodiments, the perovskite material device may be a field effect transistor (FET). The FET perovskite material device may include a source electrode, a drain electrode, a gate electrode, a dielectric layer, and a semiconductor layer. In some embodiments, the semiconductor layer of the FET perovskite material device may be a perovskite material.
[0166] According to some embodiments of the perovskite material device may optionally include one or more substrates. In some embodiments, one or both of the first and second electrodes may be coated or otherwise disposed on a substrate so that the electrode is substantially disposed between the substrate and the active layer. In various embodiments, the constituent materials of the device (e.g., substrate, electrode, active layer and / or active layer assembly) may be rigid or flexible in whole or in part. In some embodiments, the electrode may serve as a substrate, thereby eliminating the need for a separate substrate.
[0167] In addition, the perovskite material device according to certain embodiments may optionally include an anti-reflective layer or anti-reflective coating (ARC). In addition, the perovskite material device may include any one or more additives, such as any one or more of the additives described above with respect to some embodiments of the present disclosure.
[0168] Refer to part Figure 2 Describes a portion of the various materials that may be included in perovskite material devices. Figure 2 is a stylized diagram of a perovskite material device 3900 according to some embodiments. Although the various components of the device 3900 are described as comprising discrete layers of adjacent materials, it should be understood that Figure 2 is a stylized diagram; therefore, consistent with the use of "layer" discussed previously herein, embodiments according to the diagram may include such discrete layers, and / or substantially intermixed non-adjacent layers. The device 3900 includes first and second substrates 3901 and 3913. A first electrode 3902 is disposed on an inner surface of the first substrate 3901, and a second electrode 3912 is disposed on an inner surface of the second substrate 3913. An active layer 3950 is sandwiched between the two electrodes 3902 and 3912. The active layer 3950 includes a mesoporous layer 3904; first and second photoactive materials 3906 and 3908; a charge transport layer 3910, and several interface layers. Figure 2 An exemplary device 3900 is further shown in accordance with an embodiment, wherein the sublayers of the active layer 3950 are separated by an interface layer, and further wherein the interface layer is disposed on each of the electrodes 3902 and 3912. In particular, the second, third, and fourth interface layers 3905, 3907, and 3909 are disposed between each of the mesoporous layer 3904, the first photoactive material 3906, the second photoactive material 3908, and the charge transport layer 3910, respectively. The first and fifth interface layers 3903 and 3911 are disposed between (i) the first electrode 3902 and the mesoporous layer 3904; and (ii) the charge transport layer 3910 and the second electrode 3912, respectively. Thus, Figure 2 The architecture of the exemplary device depicted in can be characterized as: substrate-electrode-active layer-electrode-substrate. The architecture of active layer 3950 can be characterized as: interface layer-mesoporous layer-interface layer-photoactive material-interface layer-photoactive material-interface layer-charge transport layer-interface layer. As previously described, in some embodiments, the interface layer need not be present; alternatively, one or more interface layers may be included only between some but not all components of the active layer and / or device.
[0169] The substrate, such as one or both of the first and second substrates 3901 and 3913, can be flexible or rigid. If two substrates are included, at least one should be transparent or translucent to electromagnetic (EM) radiation (e.g., UV, visible light, or IR radiation). If one substrate is included, it can similarly be transparent or translucent, although it need not be so, as long as a portion of the device allows EM radiation to contact the active layer 3950. Suitable substrate materials include any one or more of the following: glass; sapphire; magnesium oxide (MgO); mica; polymers (e.g., PEN, PET, PEG, polyolefins, polypropylene, polyethylene, polycarbonate, PMMA, polyamide, vinyl Kapton, etc.); ceramics; carbon; composites (e.g., fiberglass, Kevlar; carbon fiber); fabrics (e.g., cotton, nylon, silk, wool); wood; drywall; tile (e.g., ceramic, composite, or clay); metal; steel; silver; gold; aluminum; magnesium; concrete; and combinations thereof.
[0170] As mentioned above, electrodes (e.g. Figure 2 One of the electrodes 3902 and 3912) can be an anode or a cathode. In some embodiments, one electrode can act as a cathode and the other can act as an anode. One or both of the electrodes 3902 and 3912 can be connected to a lead, cable, wire, or other device capable of transporting charge to and / or from the device 3900. The electrodes can be made of any conductive material, and at least one electrode should be transparent or translucent to EM radiation and / or arranged in a manner that allows EM radiation to contact at least a portion of the active layer 3950. Suitable electrode materials may include any one or more of the following: indium tin oxide or tin-doped indium oxide (ITO); fluorine-doped tin oxide (FTO); cadmium oxide (CdO); zinc indium tin oxide (ZITO); aluminum zinc oxide (AZO); aluminum (Al); gold (Au); silver (Ag); calcium (Ca); chromium (Cr); magnesium (Mg); titanium (Ti); steel; carbon (and its allotropes); doped carbon (e.g., nitrogen-doped); core-shell structured nanoparticles (e.g., silicon-carbon core-shell structures); and combinations thereof.
[0171] Mesoporous materials (e.g. Figure 2The material included in the mesoporous layer 3904 may include any material containing pores. In some embodiments, the pores may have a diameter of about 1 to about 100 nm; in other embodiments, the pore size may be about 2 to about 50 nm. Suitable mesoporous materials include any one or more of the following: any interface material and / or mesoporous material discussed elsewhere herein; aluminum (Al); bismuth (Bi); cerium (Ce); hafnium (Hf); indium (In); molybdenum (Mo); niobium (Nb); nickel (Ni); silicon (Si); titanium (Ti); vanadium (V); zinc (Zn); zirconium (Zr); oxides of any one or more of the foregoing metals (e.g., aluminum oxide, ceria, titanium dioxide, zinc oxide, zirconium oxide, etc.); sulfides of any one or more of the foregoing metals; nitrides of any one or more of the foregoing metals; and combinations thereof. In some embodiments, any material disclosed herein as an IFL may be a mesoporous material. In other embodiments, Figure 2 The device shown may not include a layer of mesoporous material and may include only a thin film or "dense" IFL that is not mesoporous.
[0172] Photoactive materials (e.g. Figure 2 The first or second photoactive material 3906 or 3908) can include any photoactive compound, such as any one or more of the following: silicon (e.g., polycrystalline silicon, single crystal silicon, or amorphous silicon), cadmium telluride, cadmium sulfide, cadmium selenide, copper indium gallium selenide, copper indium selenide, copper zinc tin sulfide, gallium arsenide, germanium, indium germanium phosphide, indium phosphide, one or more semiconductor polymers (e.g., polythiophene (e.g., poly(3-hexylthiophene) and its derivatives, or P3HT); carbazole-based copolymers such as poly(heptadecanylcarbazole dithiophene); benzothiadiazole and its derivatives (e.g., PCDTBT); other copolymers such as polycyclopentadithiophene-benzothiadiazole and its derivatives (e.g., PCPDTBT), polybenzodithiophenyl-thienothiophene-thiophene and its derivatives (e.g., PTB6, PTB7, PTB7-th, PCE-10); poly(triarylamine) compounds and their derivatives (e.g., PTAA); polyphenylene vinylene and its derivatives (e.g., MDMO-PPV, MEH-PPV), and combinations thereof.
[0173] In certain embodiments, the photoactive material may alternatively or additionally include a dye (e.g., N719, N3, other ruthenium-based dyes). In some embodiments, the dye (regardless of composition) may be applied to another layer (e.g., a mesoporous layer and / or an interfacial layer). In some embodiments, the photoactive material may include one or more perovskite materials. The photoactive substance containing the perovskite material may be in solid form, or in some embodiments it may be in the form of a dye, the dye including a suspension or solution containing the perovskite material. Such a solution or suspension may be applied to other device components in a manner similar to other dyes. In some embodiments, the solid perovskite material may be deposited by any suitable means (e.g., vapor deposition, solution deposition, direct placement of solid materials, etc.). Devices according to various embodiments may include one, two, three or more photoactive compounds (e.g., one, two, three or more perovskite materials, dyes, or combinations thereof). In certain embodiments including a plurality of dyes or other photoactive materials, each of the two or more dyes or other photoactive materials may be separated by one or more interfacial layers. In some embodiments, a plurality of dyes and / or photoactive compounds may be at least partially mixed.
[0174] Charge transport materials (e.g. Figure 2 The charge transport material of the charge transport layer 3910 in the PV device may include a solid charge transport material (i.e., informally labeled a solid electrolyte), or it may include a liquid electrolyte and / or an ionic liquid. Any liquid electrolyte, ionic liquid, and solid charge transport material may be referred to as a charge transport material. As used herein, "charge transport material" refers to any material - solid, liquid, or other - that is capable of collecting charge carriers and / or transporting charge carriers. For example, in a PV device according to some embodiments, the charge transport material is capable of transporting charge carriers to an electrode. Charge carriers may include holes (the transport of which may cause the charge transport material to be appropriately labeled as a "hole transport material") and electrons. Depending on the placement of the charge transport material relative to the cathode or anode in a PV or other device, holes may be transported toward the anode, while electrons may be transported toward the cathode. Suitable examples of charge transport materials according to some embodiments may include any one or more of the following: perovskite materials; I - / I3 -; Co complexes; polythiophenes (e.g., poly(3-hexylthiophene) and its derivatives, or P3HT); carbazole-based copolymers such as poly(heptadecanylcarbazole dithienylbenzothiadiazole) and its derivatives (e.g., PCDTBT); other copolymers such as polycyclopentadithiophene-benzothiadiazole and its derivatives (e.g., PCPDTBT), polyphenylene disulfide-thienothiophene diyl and its derivatives (e.g., PTB6, PTB7, PTB7-th, PCE-10); poly(triarylamine) compounds and their derivatives (e.g., PTAA); spiro-OMeTAD; polyphenylene vinylene and its derivatives (e.g., MDMO-PPV, MEH-PPV); fullerenes and / or fullerene derivatives (e.g., C60, PCBM); carbon nanotubes; graphite; graphene; carbon black; amorphous carbon; glassy carbon; carbon fibers; and combinations thereof. In certain embodiments, the charge transport material may include any material - solid or liquid - that is capable of collecting charge carriers (electrons or holes) and / or capable of transporting charge carriers. The charge transport material of some embodiments may therefore be an n-type or p-type active, bipolar and / or intrinsic semiconductor material. The charge transport material may be disposed adjacent to one of the electrodes of the device. Although in other embodiments, an interfacial layer may be disposed between the charge transport material and the electrode (e.g., Figure 2 , with a fifth interface layer 3911), but in some embodiments it can be disposed adjacent to an electrode. In certain embodiments, the type of charge transport material can be selected based on the electrode to which it is adjacent. For example, if the charge transport material collects and / or transports holes, it can be close to the anode in order to transport holes to the anode. However, the charge transport material can alternatively be placed near the cathode and selected or configured to transport electrons to the cathode.
[0175] As previously mentioned, devices according to various embodiments may optionally include an interfacial layer between any two other layers and / or materials, although devices according to some embodiments need not contain any interfacial layers. Thus, for example, a perovskite material device may contain zero, one, two, three, four, five, or more interfacial layers (e.g., Figure 23903, 3905, 3907, 3909, and 3911). The interfacial layers may include thin coating interfacial layers according to embodiments previously discussed herein (e.g., containing aluminum oxide and / or other metal oxide particles, and / or titanium dioxide / metal oxide bilayers, and / or other compounds according to thin coating interfacial layers as discussed elsewhere herein). Interfacial layers according to some embodiments may include any suitable material for enhancing charge transport and / or collection between two layers or materials; it may also help prevent or reduce the likelihood of charge recombination once charge has been transported away from one of the materials of an adjacent interfacial layer. Suitable interface materials may include any one or more of the following: any mesoporous material and / or interface material discussed elsewhere herein; Ag; Al; Au; B; Bi; Ca; Cd; Ce; Co; Cu; Fe; Ga; Ge; H; In; Mg; Mn; Mo; Nb; Ni; Pt; Sb; Sc; Si; Sn; Ta; Ti; V; W; Y; Zn; Zr; carbides of any of the foregoing metals (e.g., SiC, Fe3C; WC); silicides of any of the foregoing metals (e.g., Mg2Si, SrSi2, Sn2Si); oxides of any of the foregoing metals (e.g., alumina, silicon dioxide, titanium dioxide, SnO2, ZnO); sulfides of any of the foregoing metals (e.g., CdS, MoS2, SnS2); nitrides of any of the foregoing metals (e.g., Mg3N2, TiN, BN, Si3N4); selenides of any of the foregoing metals (e.g., Such as CdSe, FeS2, ZnSe); tellurides of any of the foregoing metals (such as CdTe, TiTe2, ZnTe); phosphides of any of the foregoing metals (such as InP, GaP); arsenides of any of the foregoing metals (such as CoAs3, GaAs, InGaAs, NiAs); antimonides of any of the foregoing metals (such as AlSb, GaSb, InSb); halides of any of the foregoing metals (such as CuCl, CuI, BiI3); pseudohalides of any of the foregoing metals (such as CuSCN, AuCN2); carbonates of any of the foregoing metals (such as CaCO3, Ce2(CO3)3); functionalized or non-functionalized alkylsilyl; graphite; graphene; fullerenes; carbon nanotubes; any mesoporous material and / or interface material discussed elsewhere herein; and combinations thereof (including, in some embodiments, double, triple or multiple layers of the combined material). In some embodiments, the interface layer may include a perovskite material. In addition, the interface layer may include a doped embodiment of any interface material mentioned herein (e.g., Y-doped ZnO, N-doped single-walled carbon nanotubes). The interface layer may also include a compound having three of the above materials (e.g., CuTiO3, Zn2SnO4) or a compound having four of the above materials (e.g., CoNiZnO).
[0176] As an example, Figure 3 shows a similar Figure 2 An embodiment of the structure of the perovskite material device 3900 is a perovskite material device 3900a. Figure 3 is a stylized diagram of a perovskite material device 3900a according to some embodiments. Although the various components of the device 3900a are shown as comprising discrete layers of adjacent materials, it should be understood that Figure 3 is a stylized diagram; thus, consistent with the use of "layers" discussed previously herein, embodiments according to this diagram may include such discrete layers, and / or substantially intermixed non-contiguous layers. Figure 3 In some embodiments, one or both of the active layers 3906a and 3908a may include the above relative Figure 2 Any perovskite photoactive material described. In other embodiments, one or both of the active layers 3906a and 3908a may include any photoactive material described herein, such as thin film semiconductors (e.g., CdTe, CZTS, CIGS), photoactive polymers, dye-sensitized photoactive materials, fullerenes, small molecule photoactive materials, and crystalline and polycrystalline semiconductor materials (e.g., silicon, GaAs, InP, Ge). In still other embodiments, one or both of the active layers 3906a and 3908a may include a light emitting diode (LED), a field effect transistor (FET), a thin film battery layer, or a combination thereof. In an embodiment, one of the active layers 3906a and 3908a may include a photoactive material, and the other may include a light emitting diode (LED), a field effect transistor (FET), a thin film battery layer, or a combination thereof. For example, the active layer 3908a may include a perovskite material photoactive layer, and the active layer 3906b may include a field effect transistor layer. Figure 3 Other layers shown in FIG. 3 , such as layers 3901a, 3902a, 3903a, 3904a, 3905a, 3907a, 3909a, 3910a, 3911a, 3912a, and 3913a, can be similar to those described herein with reference to Figure 2 Such corresponding layers are described.
[0177] Furthermore, in some embodiments, the perovskite material may have three or more active layers. As an example, Figure 4 shows a similar Figure 2 An implementation of a perovskite material device 3900b having a structure of the perovskite material device 3900 is shown. Figure 3 is a stylized diagram of a perovskite material device 3900b according to some embodiments. Although the various components of the device 3900b are shown as comprising discrete layers of adjacent materials, it should be understood that Figure 4is a stylized diagram; thus, consistent with the use of "layers" discussed previously herein, embodiments according to this diagram may include such discrete layers, and / or substantially intermixed non-contiguous layers. Figure 4 In some embodiments, one or more of the active layers 3904b, 3906b, and 3908b may include the active layers 3904b, 3906b, and 3908b described above. Figure 2 Any perovskite photoactive material described. In other embodiments, one or more of the active layers 3904b, 3906b, and 3908b may include any photoactive material described herein, such as thin film semiconductors (e.g., CdTe, CZTS, CIGS), photoactive polymers, dye-sensitized photoactive materials, fullerenes, small molecule photoactive materials, and crystalline and polycrystalline semiconductor materials (e.g., silicon, GaAs, InP, Ge). In yet other embodiments, one or more of the active layers 3904b, 3906b, and 3908b may include a light emitting diode (LED), a field effect transistor (FET), a thin film battery layer, or a combination thereof. In an embodiment, one or more of the active layers 3904b, 3906b, and 3908b may include a photoactive material, and the others may include a light emitting diode (LED), a field effect transistor (FET), a thin film battery layer, or a combination thereof. For example, active layers 3908a and 3906b may both include a perovskite material photoactive layer, and active layer 3904b may include a field effect transistor layer. Figure 3 Other layers shown in FIG. 3 , such as layers 3901 b, 3902 b, 3903 b, 3904 b, 3905 b, 3907 b, 3909 b, 3910 b, 3911 b, 3912 b, and 3913 b may be similar to those described herein with reference to Figure 2 Such corresponding layers are described.
[0178] Additional, more specific exemplary embodiments of perovskite devices will be discussed with respect to further stylized depictions of exemplary devices. These depictions ( Figure 1-4 ) is similarly not intended to limit the possibilities that may be implemented in some embodiments according to Figure 1-4 That is, according to any suitable means (including those explicitly discussed elsewhere herein, and other suitable means that will be apparent to those skilled in the art with the benefit of this disclosure), Figure 1-4 The architectures represented in can be modified to provide BHJs, batteries, FETs, hybrid PV cells, series multi-cell PV, parallel multi-cell PV, and other similar devices of other embodiments of the present disclosure.
[0179] Preparation of active layer of perovskite material
[0180] As previously mentioned, in some embodiments, the perovskite material in the active layer may have a formula CMX 3-y X' y (0 ≥ y ≥ 3), wherein: C comprises one or more cations (e.g., amines, ammonium, Group 1 metals, Group 2 metals, formamidinium, guanidinium, ethylenetetramine, phosphonium, imidazolium, and / or other cations or quasi-cation compounds); M comprises one or more metals (e.g., Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X and X' comprise one or more anions. In one embodiment, the perovskite material may comprise CPbI 3- y Cl y In certain embodiments, the perovskite material can be deposited onto a substrate layer by, for example, drop coating, spin coating, slot printing, screen printing, or inkjet printing using the following steps as an active layer in a PV device.
[0181] First, form a lead halide precursor ink. A certain amount of lead halide can be concentrated in a clean, dry container in a controlled atmosphere environment (e.g., a controlled atmosphere box with a glove-containing orifice that allows operating materials in an airless environment). Suitable lead halides include, but are not limited to, lead iodide (II), lead bromide (II), lead chloride (II), and lead fluoride (II). Lead halide can include a single species of lead halide, or it can include a lead halide mixture with an accurate ratio. In certain embodiments, the lead halide mixture can include iodide, bromide, chloride, or fluoride of 0.001-100 mol % of any binary, ternary, or quaternary ratio. In one embodiment, the lead halide mixture can include lead chloride (II) and lead iodide (II) at a ratio of about 10:90mol:mol. In other embodiments, the lead halide mixture can include lead chloride (II) and lead iodide (II) at a ratio of about 5:95, about 7.5:92.5, or about 15:85mol:mol.
[0182] Alternatively, other lead salt precursors may be used in combination with or in place of the lead halide salt to form the precursor ink. Suitable precursor salts may comprise lead (II) or lead (IV) with any combination of the following anions: nitrate, nitrite, carboxylate, acetate, acetonylacetonate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetrakis(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromite, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethanide, dicyanonitrosomethanide, dicyanamide, tricyanomethanide, amide, and permanganate.
[0183] The precursor ink may further contain lead (II) or lead (IV) salt in a molar ratio of 0 to 100% with respect to the following metal ions Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr as salts of the aforementioned anions.
[0184] Solvents can then be added to the container to dissolve the lead solid to form a lead halide precursor ink. Suitable solvents include, but are not limited to, anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and combinations thereof. In one embodiment, the lead solid is dissolved in anhydrous dimethylformamide (DMF). The lead solid can be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the lead solid is dissolved at about 85°C. The lead solid can be dissolved for a necessary long time to form a solution, which can occur within a time period of up to about 72 hours. The resulting solution forms a substrate (base) of the lead halide precursor ink. In some embodiments, the lead halide precursor ink can have a lead halide concentration of about 0.001M to about 10M. In one embodiment, the lead halide precursor ink has a lead halide concentration of about 1M.
[0185] Optionally, certain additives can be added to the lead halide precursor ink to affect the final perovskite crystallinity and stability. In some embodiments, the lead halide precursor ink may further include an amino acid (e.g., 5-aminopentanoic acid, histidine, glycine, lysine), an amino acid hydrohalide (e.g., 5-aminopentanoic acid hydrochloride), an IFL surface modification (SAM) agent (such as those discussed previously in the specification) or a combination thereof. In one embodiment, formamidinium chloride can be added to the lead halide precursor ink. In other embodiments, any cation halide discussed previously in the specification can be used. In some embodiments, a combination of additives can be added to the lead halide precursor ink, including, for example, a combination of formamidinium chloride and 5-aminopentanoic acid hydrochloride.
[0186] By way of explanation, and without limiting the present disclosure to any particular theory of mechanism, it has been found that when used as additives or counter cations in one-step perovskite device fabrication, formamidinium chloride and 5-aminovaleric acid improve the stability of perovskite PV devices. It has also been found that chlorides in the form of PbCl2 improve perovskite PV device performance when added to a PbI2 precursor solution in a two-step process. It has been found that the two-step perovskite thin film deposition process can be improved by adding formamidinium chloride and / or 5-aminovaleric acid hydrochloride directly to a lead halide precursor solution (e.g., PbI2) to take advantage of a single material. Other perovskite film deposition processes can likewise be improved by adding formamidinium chloride, 5-aminovaleric acid hydrochloride, or PbCl2 to a lead halide precursor solution.
[0187] The additive (including formamidinium chloride and / or 5-aminovaleric acid hydrochloride) can be added to the lead halide precursor ink at various concentrations depending on the desired properties of the resulting perovskite material. In one embodiment, the additive can be added at a concentration of about 1 nM to about 1 M. In another embodiment, the additive can be added at a concentration of about 1 μM to about 1 M. In another embodiment, the additive can be added at a concentration of about 1 μM to about 1 mM.
[0188] Optionally, in certain embodiments, water can be added to the lead halide precursor ink. As an explanation, and without limiting the present disclosure to any particular theory or mechanism, the presence of water affects the growth of perovskite thin film crystals. Under normal circumstances, water can be absorbed as water vapor from the air. However, the perovskite PV crystallinity can be controlled by adding water directly to the lead halide precursor ink at a specific concentration. Suitable water includes distilled water, deionized water, or any other water source that is substantially free of contaminants (including minerals). It has been found that, based on optical IV scanning, the light-to-electricity conversion efficiency of perovskite PV can be almost tripled by water addition compared to a completely dry device.
[0189] Water can be added to the lead halide precursor ink at various concentrations depending on the desired properties of the resulting perovskite material. In one embodiment, water can be added at a concentration of about 1 nL / mL to about 1 mL / mL. In another embodiment, water can be added at a concentration of about 1 μL / mL to about 0.1 mL / mL. In another embodiment, water can be added at a concentration of about 1 μL / mL to about 20 μL / mL.
[0190] The lead halide precursor ink can then be deposited on the desired substrate. Suitable substrate layers may include any substrate layers previously determined in the present disclosure. As described above, the lead halide precursor ink can be deposited by a variety of means, including but not limited to drip coating, spin coating, slit type printing, screen printing or inkjet printing. In certain embodiments, the lead halide precursor ink can be spin-coated to the substrate at a speed of about 500rpm to about 10,000rpm for a time of about 5 seconds to about 600 seconds. In one embodiment, the lead halide precursor ink can be spin-coated to the substrate at about 3000rpm for a time of about 30 seconds. The lead halide precursor ink can be deposited on the substrate in an ambient atmosphere within a humidity range of about 0% relative humidity to about 50% relative humidity. The lead halide precursor ink can then be dried in a substantially anhydrous atmosphere (i.e., less than 30% relative humidity) to form a film.
[0191] The film can then be thermally annealed at a temperature of about 20°C to about 300°C for a period of up to about 24 hours. In one embodiment, the film can be thermally annealed at a temperature of about 50°C for about ten minutes. The perovskite material active layer can then be completed by a conversion process in which the precursor film is immersed or rinsed with a solution comprising a solvent or solvent mixture (e.g., DMF, isopropanol, methanol, ethanol, butanol, chloroform, chlorobenzene, dimethyl sulfoxide, water) and a salt (e.g., methylammonium iodide, formamidinium iodide, guanidinium iodide, 1,2,2-triaminovinylammonium iodide, 5-aminopentanoic acid hydroiodide) at a concentration of 0.001M to 10M. In certain embodiments, the film can also be post-thermally annealed in the same manner as in the first line of this paragraph.
[0192] In some embodiments, the lead salt precursor can be deposited on a substrate to form a lead salt film. The substrate may have a temperature approximately equal to ambient temperature or a controlled temperature of 0°C to 500°C. The lead salt precursor can be deposited by a variety of methods known in the art, including but not limited to spin coating, slit printing, inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, thermal evaporation or spraying. The deposition of the lead salt precursor can be carried out in a variety of atmospheres at ambient pressure (e.g., about one atmosphere, depending on altitude and atmospheric conditions) or at a pressure less than atmospheric pressure or ambient pressure (e.g., 1 mTorr to 500 mTorr). The deposition atmosphere may include ambient air, a controlled humidity environment (e.g., 0-100 g H2O / m 3 Gas), pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination of the foregoing gases. The controlled humidity environment may include an environment in which the absolute humidity or % relative humidity is maintained at a fixed value, or in which the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In certain embodiments, deposition may be performed in a controlled humidity environment in which the % relative humidity is greater than or equal to 0% and less than or equal to 50%. In other embodiments, deposition may be performed in a controlled humidity environment containing greater than or equal to 0 g H2O / m 3 Gas and less than or equal to 20g H2O / m 3 The gas is kept in a controlled humidity environment.
[0193] The lead salt precursor can be a liquid, a gas, a solid or a combination of these states of matter, such as a solution, a suspension, a colloid, a foam, a gel or an aerosol. In some embodiments, the lead salt precursor can be a solution containing one or more solvents. For example, the lead salt precursor can contain one or more of N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and a combination thereof. The lead salt precursor can include a single lead salt (e.g., lead iodide (II), lead thiocyanate (II)) or any combination of those disclosed herein (e.g., PbI2+PbCl2; PbI2+Pb(SCN)2). The lead salt precursor may also contain one or more additives, such as an amino acid (e.g., 5-aminopentanoic acid hydroiodide), 1,8-diiodooctane, 1,8-dithiooctane, methylammonium halide, acetic acid, trifluoroacetic acid, methylammonium halide, or water. The lead halide precursor ink may be dried in a substantially anhydrous atmosphere (i.e., less than 30% relative humidity) to form a film. The film may then be thermally annealed at a temperature of about 20° C. to about 300° C. for a period of up to about 24 hours. Annealing may be performed in a variety of atmospheres at ambient pressure (e.g., about one atmosphere, depending on altitude and atmospheric conditions) or at a pressure less than atmospheric pressure or ambient pressure (e.g., 1 mTorr to 500 mTorr). The annealing atmosphere may include ambient air, a controlled humidity environment (e.g., 0-100 g H2O / m 3 Gas), pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination of the foregoing gases. The controlled humidity environment may include an environment in which the absolute humidity or % relative humidity is maintained at a fixed value, or in which the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In certain embodiments, the annealing may be performed in a controlled humidity environment in which the % relative humidity is greater than or equal to 0% and less than or equal to 50%. In other embodiments, the annealing may be performed in a controlled humidity environment containing greater than or equal to 0 g H2O / m 3 Gas and less than or equal to 20g H2O / m 3 The gas is kept in a controlled humidity environment.
[0194] After depositing the lead salt precursor, a second salt precursor (e.g., guanidinium iodide, guanidinium thiocyanate, or guanidinium thiocyanate) can be deposited onto the lead salt film, wherein the lead salt film can have a temperature approximately equal to ambient temperature or a controlled temperature of 0°C to 500°C. In some embodiments, the second salt precursor can be deposited at ambient temperature or at an elevated temperature between about 25°C and 125°C. The second salt precursor can be deposited by various methods known in the art, including but not limited to spin coating, slit printing, inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, thermal evaporation, or spraying. The deposition of the second salt precursor can be carried out in a variety of atmospheres at ambient pressure (e.g., about one atmosphere, depending on altitude and atmospheric conditions) or at a pressure less than atmospheric pressure or ambient pressure (e.g., 1 mTorr to 500 mTorr). The deposition atmosphere can include ambient air, a controlled humidity environment (e.g., 0-100 g H2O / m 3 Gas), pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination of the foregoing gases. The controlled humidity environment may include an environment in which the absolute humidity or % relative humidity is maintained at a fixed value, or in which the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In certain embodiments, deposition may be performed in a controlled humidity environment in which the % relative humidity is greater than or equal to 0% and less than or equal to 50%. In other embodiments, deposition may be performed in a controlled humidity environment containing greater than or equal to 0 g H2O / m 3 Gas and less than or equal to 20g H2O / m 3 The gas is kept in a controlled humidity environment.
[0195] In some embodiments, the second salt precursor can be a solution containing one or more solvents. For example, the second salt precursor can contain one or more of anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and combinations thereof.
[0196] After depositing the lead salt precursor and the second salt precursor, the substrate can be annealed. Annealing the substrate can convert the lead salt precursor and the second salt precursor into a perovskite material (e.g., FAPbI3, GAPb(SCN)3, FASnI3). Annealing can be performed in a variety of atmospheres at ambient pressure (e.g., about one atmosphere, depending on altitude and atmospheric conditions) or at a pressure less than atmospheric pressure or ambient pressure (e.g., 1 mTorr to 500 mTorr). The annealing atmosphere can include ambient air, a controlled humidity environment (e.g., 0-100 g H2O / m 3Gas), pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination of the foregoing gases. The controlled humidity environment may include an environment in which the absolute humidity or % relative humidity is maintained at a fixed value, or in which the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In certain embodiments, the annealing may be performed in a controlled humidity environment in which the % relative humidity is greater than or equal to 0% and less than or equal to 50%. In other embodiments, the annealing may be performed in a controlled humidity environment containing greater than or equal to 0 g H2O / m 3 Gas and less than or equal to 20g H2O / m 3 In some embodiments, the annealing may be performed at a temperature greater than or equal to 50° C. and less than or equal to 300° C. Unless otherwise described, any annealing or deposition step described herein may be performed under the aforementioned conditions.
[0197] For example, in a particular embodiment, FAPbI3 perovskite material can be formed by the following process. First, the lead halide (II) precursor comprising PbI2 and PbCl2 dissolved in anhydrous DMF at a molar ratio of about 90:10 is deposited on the substrate by spin coating or slit printing. The lead halide precursor ink is dried for about one hour (± 15 minutes) to form a film in a substantially anhydrous atmosphere (i.e., less than 30% relative humidity). The film can then be thermally annealed for about 10 minutes at a temperature of about 50°C (± 10°C). In other embodiments, the lead halide precursor can be deposited by inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation or spraying. Then, the formamidinium iodide precursor comprising 25-60mg / mL concentration of formamidinium iodide dissolved in anhydrous isopropanol can be deposited on the lead halide film by spin coating or slit printing. In other embodiments, the formamidinium iodide precursor can be deposited by inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation or spraying. After depositing the lead halide precursor and the formamidinium iodide precursor, the substrate can be heated to about 25% relative humidity (about 4 to 7 g H2O / m 3 air) and annealed at about 125°C to 200°C to form formamidinium lead iodide (FAPbI3) perovskite material.
[0198] In another embodiment, the perovskite material may comprise C'CPbX3, wherein C' is one or more Group 1 metals (i.e., Li, Na, K, Rb, Cs). In a particular embodiment, M' may be cesium (Cs). In another embodiment, C' may be rubidium (Rb). In another embodiment, C' may be sodium (Na). In another embodiment, C' may be potassium (K). In yet other embodiments, the perovskite material may comprise C' v Cw Pb y X z , wherein C' is one or more Group 1 metals, and v, w, y, and z represent real numbers from 1 to 20. In certain embodiments, the perovskite material can be deposited onto a substrate layer as an active layer in a PV device by, for example, drop coating, spin coating, gravure coating, doctor blade coating, reverse gravure coating, slot printing, screen printing, or inkjet printing using the following steps.
[0199] First, form a lead halide solution. A certain amount of lead halide can be concentrated in a clean, dry container in a controlled atmosphere environment. Suitable lead halides include but are not limited to lead iodide (II), lead bromide (II), lead chloride (II) and lead fluoride (II). Lead halide can include the lead halide of a single species, or it can include a lead halide mixture with an accurate ratio. In one embodiment, the lead halide can include lead iodide (II). In certain embodiments, the lead halide mixture can include iodide, bromide, chloride or fluoride of 0.001-100 mol % of any binary, ternary or quaternary ratio. In one embodiment, the lead halide mixture can include lead chloride (II) and lead iodide (II) with a ratio of about 10:90mol:mol. In other embodiments, the lead halide mixture can include lead chloride (II) and lead iodide (II) with a ratio of about 5:95, about 7.5:92.5 or about 15:85mol:mol.
[0200] Alternatively, other lead salt precursors may be used in combination with or in place of the lead halide salt to form the lead salt solution. Suitable precursor salts may comprise lead (II) or lead (IV) with any combination of the following anions: nitrate, nitrite, carboxylate, acetate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetrakis(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromite, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitrosomethane, dicyanamide, tricyanomethane, amide, and permanganate.
[0201] The lead salt solution may further contain lead (II) or lead (IV) salt in a molar ratio of 0 to 100% of the following metal ions Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr as salts of the aforementioned anions.
[0202] Solvents can then be added to the container to dissolve the lead solid to form the lead halide solution. Suitable solvents include, but are not limited to, anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide (DMF), dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and combinations thereof. In one embodiment, the lead solid is dissolved in anhydrous dimethylformamide (DMF). The lead halide solid can be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the lead halide solid is dissolved at about 85°C. The lead halide solid can dissolve the necessary long time to form a solution, which can occur within a time period of up to about 72 hours. The resulting solution forms a substrate for the lead halide precursor ink. In some embodiments, the lead halide precursor ink can have a lead halide concentration of about 0.001M to about 10M. In one embodiment, the lead halide precursor ink has a lead halide concentration of about 1 M. In some embodiments, the lead halide solution may further include an amino acid (e.g., 5-aminovaleric acid, histidine, glycine, lysine), an amino acid hydrohalide salt (e.g., 5-aminovaleric acid hydrochloride), an IFL surface modification (SAM) agent (such as those discussed previously in the specification), or a combination thereof.
[0203] Next, a Group 1 metal halide solution is formed. A certain amount of Group 1 metal halide can be concentrated in a clean, dry container in a controlled atmosphere environment. Suitable Group 1 metal halides include, but are not limited to, cesium iodide, cesium bromide, cesium chloride, cesium fluoride, rubidium iodide, rubidium bromide, rubidium chloride, rubidium fluoride, lithium iodide, lithium bromide, lithium chloride, lithium fluoride, sodium iodide, sodium bromide, sodium chloride, sodium fluoride, potassium iodide, potassium bromide, potassium chloride, potassium fluoride. Group 1 metal halides can include a single species of Group 1 metal halides, or they can include a Group 1 metal halide mixture in an accurate ratio. In one embodiment, the Group 1 metal halide can include cesium iodide. In another embodiment, the Group 1 metal halide can include rubidium iodide. In another embodiment, the Group 1 metal halide can include sodium iodide. In another embodiment, the Group 1 metal halide may comprise potassium iodide.
[0204] Alternatively, other Group 1 metal salt precursors may be used in combination with or in place of the Group 1 metal halide salt to form the Group 1 metal salt solution. Suitable precursor Group 1 metal salts can comprise a Group 1 metal and any combination of the following anions: nitrate, nitrite, carboxylate, acetate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetrakis(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromite, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethanide, dicyanonitrosomethanide, dicyanamide, tricyanomethanide, amide, and permanganate.
[0205] A solvent may then be added to the container to dissolve the Group 1 metal halide solid to form a Group 1 metal halide solution. Suitable solvents include, but are not limited to, anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide (DMF), dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and combinations thereof. In one embodiment, the lead solid is dissolved in anhydrous dimethyl sulfoxide (DMSO). The Group 1 metal halide solid may be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the Group 1 metal halide solid is dissolved at room temperature (i.e., about 25°C). The Group 1 metal halide solid may be dissolved for a time period of a desired length to form a solution, which may occur within a time period of up to about 72 hours. The resulting solution forms a Group 1 metal halide solution. In some embodiments, the Group 1 metal halide solution may have a Group 1 metal halide concentration of about 0.001 M to about 10 M. In one embodiment, the Group 1 metal halide solution has a Group 1 metal halide concentration of about 1 M. In some embodiments, the Group 1 metal halide solution may further comprise an amino acid (e.g., 5-aminopentanoic acid, histidine, glycine, lysine), an amino acid hydrohalide salt (e.g., 5-aminopentanoic acid hydrochloride), an IFL surface modification (SAM) agent (such as those discussed previously in the specification), or a combination thereof.
[0206] Next, the lead halide solution and the Group 1 metal halide solution are mixed to form a thin film precursor ink. The lead halide solution and the Group 1 metal halide solution may be mixed at a ratio such that the molar concentration of the Group 1 metal halide of the resulting thin film precursor ink is 0% to 25% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 1% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 5% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 10% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 15% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 20% of the molar concentration of the lead halide. In a particular embodiment, the thin film precursor ink can have a molar concentration of the Group 1 metal halide that is 25% of the molar concentration of the lead halide.In some embodiments, the lead halide solution and the Group 1 metal halide solution can be stirred or agitated during or after mixing.
[0207] The film precursor ink can then be deposited on the desired substrate. Suitable substrate layers can include any substrate layer previously determined in the present disclosure. As described above, the film precursor ink can be deposited by a variety of means, including but not limited to drip coating, spin coating, gravure coating, scraping, reverse gravure coating, slit printing, screen printing or inkjet printing. In certain embodiments, the film precursor ink can be spin-coated onto the substrate at a speed of about 500rpm to about 10,000rpm for a time of about 5 seconds to about 600 seconds. In one embodiment, the film precursor ink can be spin-coated onto the substrate at about 3000rpm for a time of about 30 seconds. The film precursor ink can be deposited on the substrate in an ambient atmosphere within a humidity range of about 0% relative humidity to about 50% relative humidity. The film precursor ink can then be placed in a substantially anhydrous atmosphere (i.e., less than 30% relative humidity or 7g H2O / m 3 ) to form a film.
[0208] The film can then be thermally annealed at a temperature of about 20°C to about 300°C for a period of up to about 24 hours. In one embodiment, the film can be thermally annealed at a temperature of about 50°C for about ten minutes. The perovskite material active layer can then be completed by a conversion process in which the precursor film is immersed or rinsed with a solution comprising a solvent or a solvent mixture (e.g., DMF, isopropanol, methanol, ethanol, butanol, chloroform, chlorobenzene, dimethyl sulfoxide, water) and a salt (e.g., methylammonium iodide, formamidinium iodide, guanidinium iodide, 1,2,2-triaminovinylammonium iodide, 5-aminopentanoic acid hydroiodide) at a concentration of 0.001M to 10M. In certain embodiments, the perovskite material film can also be post-thermally annealed in the same manner as in the first line of this paragraph.
[0209] In some embodiments, the salt solution can be prepared by concentrating the salt in a clean, dry container in a controlled atmosphere environment. Suitable salts include, but are not limited to, methylammonium iodide, formamidinium iodide, guanidinium iodide, imidazolium iodide, ethylenetetramine iodide, 1,2,2-triaminovinyl ammonium iodide, and 5-aminopentanoic acid hydroiodide. Other suitable salts can include any organic cation described above in the section entitled "perovskite material". The salt can include a single species of salt, or it can include a salt mixture in an accurate ratio. In one embodiment, the salt can include methylammonium iodide. In another embodiment, the salt can include formamidinium iodide. Next, a solvent can be subsequently added to a container to dissolve the salt solid to form a salt solution. Suitable solvents include, but are not limited to, DMF, isopropanol, methanol, ethanol, butanol, chloroform, chlorobenzene, dimethyl sulfoxide, water, and combinations thereof. In one embodiment, the formamidinium iodide salt solid is dissolved in isopropanol. The salt solid can be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the salt solid dissolves at room temperature (i.e., about 25°C). The salt solid can dissolve for a time required to form a solution, which can occur within a time period of up to about 72 hours. The resulting solution forms the salt solution. In some embodiments, the salt solution can have a salt concentration of about 0.001M to about 10M. In one embodiment, the salt solution has a salt concentration of about 1M.
[0210] For example, lead (II) iodide solution, cesium iodide solution and methylammonium (MA) iodide salt solution can be used to obtain a compound having the formula Cs i MAPbI3 perovskite material, wherein i is equal to a number from 0 to 1. As another example, a lead (II) iodide solution, a rubidium iodide solution, and a formamidinium iodide (FA) salt solution can be used to obtain a perovskite material having the formula Rb iA perovskite material of the formula Cs can be obtained using a lead (II) iodide solution, a cesium iodide solution, and a formamidinium iodide (FA) salt solution. i A perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1. As another example, a lead (II) iodide solution, a potassium iodide solution, and a formamidinium iodide (FA) salt solution can be used to obtain a perovskite material having the formula K i FAPbI3 perovskite material, wherein i is equal to a number from 0 to 1. As another example, a lead (II) iodide solution, a sodium iodide solution, and a formamidinium iodide (FA) salt solution can be used to obtain a perovskite material having the formula Na i FAPbI3 perovskite material, wherein i is equal to a number from 0 to 1. As another example, a lead (II) iodide-lead (II) chloride mixture solution, a cesium iodide solution, and a formamidinium iodide (FA) salt solution can be used to obtain a perovskite material having the formula Cs i FqV 3-y Cl y A perovskite material, wherein i is equal to a number from 0 to 1, and y represents a number from 0 to 3.
[0211] In a specific embodiment, the lead halide solution as described above can have a molar ratio of PbI2 to PbCl2 of 90:10. Cesium iodide (CsI) solution can be added to the lead halide solution to form a thin film precursor ink containing 10 mol% of CsI by the above method. FAPbI3 perovskite material can be prepared using the thin film precursor solution according to the above method. Chloride anions and cesium atoms can be incorporated into the FAPbI3 lattice by adding cesium ions through the CsI solution as described above. Compared with adding cesium or rubidium ions without adding chloride ions as described above, this can lead to a greater degree of lattice contraction. Table 1 below shows the lattice parameters of FAPbI3 perovskite materials with 10 mol% of rubidium and 20 mol% of chloride (e.g., 10 mol% of PbCl2), 10 mol% of cesium and 10 mol% of cesium and 20 mol% of chloride, wherein the mole % concentration represents the concentration of the additive relative to the lead atoms in the lead halide solution. It can be seen from Table 1 that the FAPbI3 perovskite material with added cesium and chloride has a lattice parameter smaller than that of the other two perovskite material samples.
[0212] Table 1
[0213]
[0214] In addition, the data indicate that the FAPbI3 perovskite material with the addition of rubidium, cesium and / or chloride has a Pm3-m cubic structure. It has been observed that FAPbI3 perovskites containing up to and including 10 mol% Rb and 10 mol% Cl, or 10 mol% Cs, or 10 mol% Cs and 10 mol% Cl maintain a cubic Pm3-m cubic crystal structure. Fig.29 Shown are x-ray diffraction patterns corresponding to each sample provided in Table 1. Tables 2-4 provide the x-ray diffraction peaks and intensities for the three perovskite materials shown in Table 1. The data were collected at ambient conditions on a Rigaku Miniflex 600 using a Cu Ka radiation source at a scan rate of 1.5° 2θ / min.
[0215] Table 2
[0216] Table 3
[0217]
[0218] Table 4
[0219]
[0220] The lattice constant under Cu Kα radiation is The geometrically expected x-ray diffraction patterns of the cubic Pm3-m materials are shown in Table 5. From the data, it can be seen that the perovskite materials prepared using 10 mol% Rb and 10 mol% Cl, 10 mol% Cs, and 10% Cs and 10% Cl each have a diffraction pattern that conforms to the expected pattern of the cubic Pm3-m perovskite material.
[0221] Table 5
[0222]
[0223] Enhanced perovskite
[0224] When the perovskite is formulated with organic cations having longer alkyl chains than the methylammonium and formamidinium cations described above, so-called "layered" 2D perovskites are known to form. Layered 2D perovskites include structures such as Ruddlesden-Popper phases, Dion-Jacobson phases, and Aurivillius phases. For example, by replacing methylammonium or the other cations described above with 1-butylammonium, Ruddlesden-Popper 2D perovskites can be obtained in a "one-step" process (not described herein) to form perovskites. In such perovskites, 1-butylammonium prevents the perovskite from forming a completely crystalline lattice, but instead causes the perovskite to form in the form of a perovskite "sheet" having a single crystal structural thickness. Figure 5The structure of the Ruddlesden-Popper perovskite 5500 with a 1-butylammonium cation 5510 is shown. Figure 5 As can be seen in the figure, the "tail" of the butylammonium cation 5510 causes the lead and iodide ion portion of the perovskite material to separate from the other lead and iodide ion structures, resulting in a "sheet" of 2D perovskite. Therefore, if the Ruddlesden-Popper form of the perovskite is not desired, the introduction of "bulky organic" cations (such as 1-butylammonium or benzylammonium) during the formation of the perovskite material may be undesirable.
[0225] However, adding a dilute amount of 1-butylammonium solution before annealing the perovskite material can lead to Figure 6 The perovskite shown in . Figure 6 An embodiment of a perovskite material 2000 with the addition of alkylammonium cations for surface passivation is shown. In the illustrated embodiment, the surface of the formamidinium lead iodide (FAPbI3) perovskite material 2010 is shown with 1-butylammonium cations 2020 at the surface. In some embodiments, the 1-butylammonium cations (or other "bulky" organic cations described herein) can diffuse into the perovskite material near the surface of the perovskite material lattice. In a specific embodiment, the 1-butylammonium cations (or other "bulky" organic cations described herein) can be located in the perovskite material 50 nanometers or less from the lattice surface or grain boundary. The inclusion of "bulky" organic cations (such as 1-butylammonium) near or at the surface of the perovskite material can cause the chemical formula of the perovskite material to deviate from the "ideal" stoichiometric ratio of the perovskite material disclosed herein. For example, the inclusion of such organic cations can cause the perovskite material to have a substoichiometric or superstoichiometric chemical formula relative to the CMX3 chemical formula described herein. In this case, the general formula of the perovskite material can be expressed as C x M y X z , where x, y, and z are real numbers. In some embodiments, the perovskite material may have the formula C'2C n-1 M n X 3n-1 , wherein n is an integer. For example, when n=1, the perovskite material may have a formula of C'2MX4, when n=2, the perovskite material may have a formula of C'2CM2X7, and when n=3, the perovskite material may have a formula of C'2C2M3X 10 When n=4, the perovskite material may have the formula C'2C3M4X 13 Etc. Fig.30 As shown, the value of n represents the thickness of the inorganic metal halide sublattice of the perovskite material. n-1 M n X3n-1 Phases of the perovskite material can be formed in regions where bulk organic cations have diffused or otherwise entered the crystal lattice of the perovskite material. For example, such phases can exist within 50 nanometers of a lattice surface (e.g., a surface or grain boundary) of an already formed perovskite material including bulk organic cations disclosed herein.
[0226] The carbon "tail" of the 1-butylammonium ion can provide protective properties to the surface by effectively keeping other molecules away from the perovskite surface. In some embodiments, the alkyl "tail" of the 1-butylammonium ion can be oriented away from or parallel to the surface of the perovskite material. In particular, the 1-butylammonium "tail" is hydrophobic, which prevents water molecules from contacting the perovskite surface and protects the surface of the perovskite material 2010 from the influence of water in the environment. In addition, the 1-butylammonium cation can also be used to passivate the surface and any grain boundaries or defects of the perovskite material 2010. Passivation refers to the electrical properties of preventing charge accumulation or "trap states" at the surface or grain boundaries of the perovskite material 2010. By being used to passivate the portion of the perovskite material 2010, 1-butylammonium can be beneficial to improve the charge transfer in and out of the perovskite material 2010, and improve the electrical properties of the photoactive layer.
[0227] In some embodiments, other organic cations may be applied to replace or combine with 1-butylammonium. Examples of other "bulky organic" cations that may be used to surface passivate perovskite materials include, but are not limited to, ethylammonium, propylammonium, n-butylammonium; perylene n-butylamine-imide; butane-1,4-diammonium; 1-pentylammonium; 1-hexylammonium; poly(vinylammonium); phenethylammonium; 3-phenyl-1-propylammonium; 4-phenyl-1-butylammonium; 1,3-dimethylbutylammonium; 3,3-dimethylbutylammonium; 1-heptylammonium; 1-octylammonium; 1-nonylammonium; 1-decylammonium; and 1-eicosylammonium. In addition, bulky organic cations having a tail containing one or more heteroatoms in addition to the cationic species may be coordinated, bonded, or integrated with the perovskite material lattice. The heteroatom may be any atom in the tail that is not hydrogen or carbon, including nitrogen, sulfur, oxygen, or phosphorus.
[0228] Other examples of "bulky" organic cations may include the following molecules functionalized with ammonium groups, phosphonium groups, or other cationic groups that can be incorporated into the surface "C-sites" of the perovskite material: benzene, pyridine, naphthalene, anthracene, xanthene, phenanthrene, tetracene, Benzanthracene, benzo[c]phenanthrene, triphenylene, pyrene, perylene, coronene, substituted dicarboxylic acid imides, aniline, N-(2-aminoethyl)-2-isoindole-1,3-dione, 2-(1-aminoethyl)naphthalene, 2-triphenylene-O-ethylamine ether, benzylamine, benzyl ammonium salt, N-butyl-N'-4-aminobutylperylene-3,4,9,10-bis(dicarboximide), 1-(4-alkylphenyl) Methylamine, 1-(4-alkyl-2-phenyl)ethylamine, 1-(4-alkylphenyl)methylamine, 1-(3-alkyl-5-alkylphenyl)methylamine, 1-(3-alkyl-5-alkyl-2-phenyl)ethylamine, 1-(4-alkyl-2-phenyl)ethylamine, 2-ethylamine-7-alkyl-naphthalene, 2-ethylamine-6-alkyl-naphthalene, 1-ethylamine-7-alkyl-naphthalene, 1-ethylamine-6-alkyl-naphthalene, 2- Methylamine-7-alkyl-naphthalene, 2-methylamine-6-alkyl-naphthalene, 1-methylamine-7-alkyl-naphthalene, 1-methylamine-6-alkyl-naphthalene, Nn-aminoalkyl-N'-4-aminobutylperylene-3,4,9,10-bis(dicarboximide), 1-(3-butyl-5-methoxybutylphenyl)methylamine, 1-(4-pentylphenyl)methylamine, 1-[4-(2-methylpentyl)-2-phenyl]ethylamine Amine, 1-(3-butyl-5-pentyl-2-phenyl)ethylamine, 2-(5-[4-methylpentyl]-2-naphthyl)ethylamine, N-7-tridecyl-N'-4-aminobutylperylene-3,4,9,10-bis(dicarboximide), N-n-heptyl-N'-4-aminobutylperylene-3,4,9,10-bis(dicarboximide), 2-(6-[3-methoxypropyl]-2-naphthyl)ethylamine. According to certain embodiments, Figure 17-28 Provides illustrations of the structures of these organic molecules. Fig.17 and 18 , each "R group" R x can be any of =H, R', Me, Et, Pr, Ph, Bz, F, Cl, Br, I, NO2, OR', NR'2, SCN, CN, N3, SR', wherein R' can be an alkyl, alkenyl or alkynyl chain. In addition, at least one of the R x The group can be (CH2) n EX y or (CH2) n C(EX y )2, where n and y = 0, 1, 2 or greater, and n and y may be equal or unequal. In addition, referring to Fig.19, the molecules shown may include any hydrohalide salt of each of the shown amines, such as benzyl ammonium salts, where the X group shown may be F, Cl, Br, I, SCN, CN or any other pseudohalide. Other acceptable anions other than halide ions may include nitrate, nitrite, carboxylate, acetate, acetonylacetonate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetrakis(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromite, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitrosomethane, dicyanamide, tricyanomethane, amide, and permanganate. Suitable R groups may also include, but are not limited to, hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne C x H y , wherein x=1-20, y=1-42, cyclic, branched or linear; alkyl halide C x H y X z , x=1-20, y=0-42, z=1-42, X=F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen in the ring (e.g. pyridine, pyrrole, pyrrolidine, piperidine, tetrahydroquinoline); any sulfur-containing group (e.g. sulfoxide, thiol, alkylsulfide); any nitrogen-containing group (nitroxide, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g. boric acid); any organic acid (e.g. acetic acid, propionic acid); and its ester or amide derivatives; any amino acid (e.g. glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammoniopentanoic acid), including α, β, γ and higher derivatives; any silicon-containing group (e.g. siloxane); and any alkoxy or group -OC x H y , where x=0-20, y=1-42.
[0229] Furthermore, in some embodiments, the bulky organic cations can passivate grain boundaries and surface defects in the perovskite material. Figure 7 An exemplary embodiment of a perovskite material layer 3000 is shown in which 1-butylammonium 3020 passivates the surface and grain boundaries 3015 of the bulk perovskite material 3010. As described above, the alkyl tails of these ions can also form a hydrophobic layer that repels water and other polar species and prevents such species from reaching the surface of the perovskite material. Figure 7As can be seen in FIG. 3 , the “tail” of the bulky organic cation may not be chemically connected (e.g., covalently or ionically bonded) to the surface or grain boundary 3015 of the perovskite material layer 3000. As used herein, the “tail” of any bulky organic cation refers to the non-ionic carbon structure of the bulky organic cation. For example, the tail of 1-butylammonium is butyl, and the tail of benzylammonium is benzyl.
[0230] The tail of the bulky organic cation can also be arranged in other ways relative to the surface or grain boundary of the perovskite material. Typically, the cation "head" of the bulky organic cation will not diffuse across the surface or grain boundary of the perovskite material more than 50 nanometers. The tail can interact weakly with the perovskite material and be oriented away from the surface of the perovskite material grain. The tail can have intermolecular interactions (such as dipole-dipole or hydrogen bonds) with the surface of the perovskite material grain, resulting in a structure in which the tail is oriented toward the surface of the perovskite material grain. In some embodiments, the tails of some bulky organic cations present in the perovskite material may not interact with the surface or grain boundary of the perovskite material, and the tails of other bulky organic cations in the perovskite material can interact with the surface or grain boundary of the perovskite material. The tail may contain a heteroatom or an anion (i.e., a zwitterion) having at least one lone electron pair, which may covalently interact (i.e., coordinate covalent bonds) with the surface of the perovskite material grains via metal atoms (e.g., Pb, Sn, Ge, In, Bi, Cu, Ag, Au) present in the perovskite material. The tail may also include cationic species, such as diammonium butane as described herein, which may be incorporated into the perovskite material by substitution (e.g., guanidine) at at least two "C" cation sites. The tail including cationic species may also bridge two layers of a 2D perovskite material, tending to span the grain surface of the perovskite material, or orienting away from the grain surface of the perovskite material in a manner similar to that described with reference to the non-ionic tail. In another embodiment, a bulky organic cation (e.g., an imidazolium cation) having a sufficiently large tail volume may simply stay on the perovskite surface or grain boundary without diffusing into the perovskite material.
[0231] Furthermore, in other embodiments, bulky organic cations having tail groups of varying lengths or sizes may be applied to the perovskite to passivate grain boundaries and surface defects in the perovskite material. Figure 8 An exemplary embodiment of a perovskite material layer 4000 is shown having a combination of 1-butylammonium 4020, 1-nonylammonium 4021, 1-heptylammonium 4022, and 1-hexylammonium 4023 passivating the surface and grain boundaries 4015 of a bulk perovskite material 4010. In certain embodiments, any mixture of the alkylammonium compounds identified above may be applied to the perovskite materials described herein. Figure 8An exemplary embodiment of a perovskite material layer 4000 is shown having a combination of 1-butylammonium 4020, 1-nonylammonium 4021, 1-heptylammonium 4022, and 1-hexylammonium 4023 that passivate the surface and grain boundaries 4015 of the bulk perovskite material 4010. In certain embodiments, any mixture of the alkylammonium compounds identified above can be applied to the perovskite material described herein. In some embodiments, the bulky organic cation can include a benzyl group. Fig. 8A An exemplary embodiment of a perovskite material layer 4500 having multiple bulky organic cations containing benzyl groups that passivate the surface and grain boundaries 4515 of the bulk perovskite material 4510 is shown.
[0232] Adding a 1-butylammonium surface coating to a perovskite material as described above has been shown to improve the high temperature durability of the perovskite in humid environments. Fig. 9 A comparison of images taken of perovskite materials with and without a 1-butylammonium ("BAI") surface coating over a period of 48 days is shown. The two perovskite materials have the same composition and were exposed to an environment with a temperature of 85°C and a relative humidity of 55% for 48 days. As can be seen from the photographs, the perovskite material without the 1-butylammonium surface coating became significantly lighter in color after one day of exposure to the environment, indicating that the perovskite material has been significantly degraded. The perovskite material with the 1-butylammonium surface coating showed a gradual lightening of color over 48 days and remained partially dark after 48 days. This indicates that the perovskite material with the 1-butylammonium surface coating is more robust than the perovskite material without the 1-butylammonium surface coating during long-term exposure to a high temperature environment.
[0233] Fig.10 A comparison of images taken of perovskite materials with and without a 1-butylammonium ("BAI") surface coating over a period of seven days is shown. The two perovskite materials have the same composition and were exposed to an environment with a temperature of 85°C and a relative humidity of 0% for 7 days. As can be seen from the photographs, the perovskite material without the 1-butylammonium surface coating became significantly lighter in color after one day of exposure to the environment, indicating that the perovskite material has been significantly degraded. The perovskite material with the 1-butylammonium surface coating showed minimal color change after 7 days. This indicates that the perovskite material with the 1-butylammonium surface coating did not completely decompose during long-term exposure to a high temperature and high humidity environment.
[0234] In other embodiments, perylene n-butylamine-imide may be applied to the surface of the perovskite material as described above for 1-butylammonium. Fig.11A -D shows various perylene monoimides and diimides that can be applied to the surface of the perovskite material according to the present disclosure. Fig.12An embodiment of a perovskite material 2500 with the addition of alkylammonium cations for surface passivation is shown. In the embodiment shown, the surface of the formamidinium lead iodide (FAPbI3) perovskite material 2510 is shown with perylene n-butylamine-imide 2520 at the surface. Figure 6 , the carbon "tail" of the perylene-n-butylamine-imide ion can provide protective properties to the perovskite surface by effectively keeping other molecules away from the surface. In particular, the perylene-n-butylamine-imide "tail" is hydrophobic, which prevents water molecules from contacting the perovskite surface and protects the surface of the perovskite material 2510 from water in the environment. In addition, the perylene-n-butylamine-imide cation can also be used to passivate the surface of the perovskite material 2510 and any grain boundaries or defects. By being used to passivate portions of the perovskite material 2510, the perylene-n-butylamine-imide can facilitate improved charge transfer in and out of the perovskite material 2510 and improve the electrical properties of the photoactive layer.
[0235] An exemplary method of depositing 1-butylammonium prior to annealing the perovskite material is described below.
[0236] First, form a lead halide precursor ink. A certain amount of lead halide can be concentrated in a clean, dry container in a controlled atmosphere environment (e.g., a controlled atmosphere box with a glove-containing orifice that allows operating materials in an airless environment). Suitable lead halides include, but are not limited to, lead iodide (II), lead bromide (II), lead chloride (II), and lead fluoride (II). Lead halide can include a single species of lead halide, or it can include a lead halide mixture with an accurate ratio. In certain embodiments, the lead halide mixture can include iodide, bromide, chloride, or fluoride of 0.001-100 mol % of any binary, ternary, or quaternary ratio. In one embodiment, the lead halide mixture can include lead chloride (II) and lead iodide (II) at a ratio of about 10:90mol:mol. In other embodiments, the lead halide mixture can include lead chloride (II) and lead iodide (II) at a ratio of about 5:95, about 7.5:92.5, or about 15:85mol:mol.
[0237] Alternatively, other lead salt precursors may be used in combination with or in place of the lead halide salt to form the precursor ink. Suitable precursor salts may comprise lead (II) or lead (IV) with any combination of the following anions: nitrate, nitrite, carboxylate, acetate, acetonylacetonate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetrakis(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromite, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethanide, dicyanonitrosomethanide, dicyanamide, tricyanomethanide, amide, and permanganate.
[0238] The precursor ink may further contain lead (II) or lead (IV) salt in a molar ratio of 0 to 100% of the following metal ions Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr as salts of the aforementioned anions.
[0239] Then, a solvent may be added to dissolve the lead solid to form a lead halide precursor ink. Suitable solvents include, but are not limited to, anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and combinations thereof. In one embodiment, the lead solid is dissolved in anhydrous dimethylformamide (DMF). The lead solid may be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the lead solid is dissolved at about 85°C. The lead solid may be dissolved for a necessary long time to form a solution, which may occur within a time period of up to about 72 hours. The resulting solution forms a substrate for the lead halide precursor ink. In some embodiments, the lead halide precursor ink may have a lead halide concentration of about 0.001M to about 10M. In one embodiment, the lead halide precursor ink has a lead halide concentration of about 1M.
[0240] Optionally, certain additives can be added to the lead halide precursor ink to affect the final perovskite crystallinity and stability. In some embodiments, the lead halide precursor ink may further include an amino acid (e.g., 5-aminopentanoic acid, histidine, glycine, lysine), an amino acid hydrohalide (e.g., 5-aminopentanoic acid hydrochloride), an IFL surface modification (SAM) agent (such as those discussed previously in the specification) or a combination thereof. In one embodiment, formamidinium chloride can be added to the lead halide precursor ink. In other embodiments, any cation halide discussed previously in the specification can be used. In some embodiments, a combination of additives can be added to the lead halide precursor ink, including, for example, a combination of formamidinium chloride and 5-aminopentanoic acid hydrochloride.
[0241] The additive (including formamidinium chloride and / or 5-aminovaleric acid hydrochloride) can be added to the lead halide precursor ink at various concentrations depending on the desired properties of the resulting perovskite material. In one embodiment, the additive can be added at a concentration of about 1 nM to about 1 M. In another embodiment, the additive can be added at a concentration of about 1 μM to about 1 M. In another embodiment, the additive can be added at a concentration of about 1 μM to about 1 mM.
[0242] In some embodiments, a Group 1 metal halide solution to be added to the lead halide precursor ink is formed. A certain amount of Group 1 metal halide can be concentrated in a clean, dry container in a controlled atmosphere environment. Suitable Group 1 metal halides include, but are not limited to, cesium iodide, cesium bromide, cesium chloride, cesium fluoride, rubidium iodide, rubidium bromide, rubidium chloride, rubidium fluoride, lithium iodide, lithium bromide, lithium chloride, lithium fluoride, sodium iodide, sodium bromide, sodium chloride, sodium fluoride, potassium iodide, potassium bromide, potassium chloride, potassium fluoride. The Group 1 metal halide can contain a single species of Group 1 metal halide, or it can contain a mixture of Group 1 metal halides in an accurate ratio. In one embodiment, the Group 1 metal halide can contain cesium iodide. In another embodiment, the Group 1 metal halide can contain rubidium iodide. In another embodiment, the Group 1 metal halide can contain sodium iodide. In another embodiment, the Group 1 metal halide may comprise potassium iodide.
[0243] Alternatively, other Group 1 metal salt precursors may be used in combination with or in place of the Group 1 metal halide salt to form the Group 1 metal salt solution. Suitable precursor Group 1 metal salts can comprise a Group 1 metal and any combination of the following anions: nitrate, nitrite, carboxylate, acetate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetrakis(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromite, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethanide, dicyanonitrosomethanide, dicyanamide, tricyanomethanide, amide, and permanganate.
[0244] A solvent may then be added to the container to dissolve the Group 1 metal halide solid, thereby forming a Group 1 metal halide solution. Suitable solvents include, but are not limited to, anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide (DMF), dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and combinations thereof. In one embodiment, the lead solid is dissolved in anhydrous dimethyl sulfoxide (DMSO). The Group 1 metal halide solid may be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the Group 1 metal halide solid is dissolved at room temperature (i.e., about 25°C). The Group 1 metal halide solid may be dissolved for a time period required to form a solution, which may occur within a time period of up to about 72 hours. The resulting solution forms a Group 1 metal halide solution. In some embodiments, the Group 1 metal halide solution may have a Group 1 metal halide concentration of about 0.001 M to about 10 M. In one embodiment, the Group 1 metal halide solution has a Group 1 metal halide concentration of about 1 M. In some embodiments, the Group 1 metal halide solution may further comprise an amino acid (e.g., 5-aminopentanoic acid, histidine, glycine, lysine), an amino acid hydrohalide salt (e.g., 5-aminopentanoic acid hydrochloride), an IFL surface modification (SAM) agent (such as those discussed previously in the specification), or a combination thereof.
[0245] Next, the lead halide solution and the Group 1 metal halide solution are mixed to form a thin film precursor ink. The lead halide solution and the Group 1 metal halide solution may be mixed at a ratio such that the molar concentration of the Group 1 metal halide of the resulting thin film precursor ink is 0% to 25% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 1% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 5% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 10% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 15% of the molar concentration of the lead halide. In a specific embodiment, the thin film precursor ink may have a molar concentration of the Group 1 metal halide of 20% of the molar concentration of the lead halide. In a particular embodiment, the thin film precursor ink can have a molar concentration of the Group 1 metal halide that is 25% of the molar concentration of the lead halide.In some embodiments, the lead halide solution and the Group 1 metal halide solution can be stirred or agitated during or after mixing.
[0246] Optionally, in certain embodiments, water can be added to the lead halide precursor ink. As an explanation, and without limiting the present disclosure to any particular theory or mechanism, the presence of water affects the growth of perovskite thin film crystals. Under normal circumstances, water can be absorbed as water vapor from the air. However, the perovskite PV crystallinity can be controlled by adding water directly to the lead halide precursor ink at a specific concentration. Suitable water includes distilled water, deionized water, or any other water source that is substantially free of contaminants (including minerals). It has been found that, based on optical IV scanning, the light-to-electricity conversion efficiency of perovskite PV can be almost tripled by water addition compared to a completely dry device.
[0247] Water can be added to the lead halide precursor ink at various concentrations depending on the desired properties of the resulting perovskite material. In one embodiment, water can be added at a concentration of about 1 nL / mL up to about 1 mL / mL. In another embodiment, water can be added at a concentration of about 1 μL / mL to about 0.1 mL / mL. In another embodiment, water can be added at a concentration of about 1 μL / mL to about 20 μL / mL.
[0248] The lead halide precursor ink or the film precursor ink can then be deposited on the desired substrate. Suitable substrate layers may include any substrate layer previously determined in the present disclosure. As described above, the lead halide precursor ink or the film precursor ink can be deposited by a variety of means, including but not limited to drip coating, spin coating, slit type printing, screen printing or inkjet printing. In certain embodiments, the lead halide precursor ink or the film precursor ink can be spin-coated to a substrate at a speed of about 500rpm to about 10,000rpm for a time of about 5 seconds to about 600 seconds. In one embodiment, the lead halide precursor ink or the film precursor ink can be spin-coated to a substrate at about 3000rpm for a time of about 30 seconds. In some embodiments, multiple subsequent depositions of the precursor ink can be performed to form a film layer. The lead halide precursor ink or the film precursor ink can be deposited on a substrate in an ambient atmosphere within a humidity range of about 0% relative humidity to about 50% relative humidity. The lead halide precursor ink or the thin film precursor ink may then be dried in a substantially water-free atmosphere (ie, less than 30% relative humidity) to form a thin film.
[0249] After the lead halide precursor or thin film precursor is deposited, a bulky organic cation as described above (e.g., benzyl ammonium, phenethyl ammonium, ethyl ammonium, propyl ammonium, n-butyl ammonium; butane-1,4-diammonium; 1-pentylammonium; 1-hexylammonium; poly(vinylammonium); phenethylammonium; 3-phenyl-1-propylammonium; 4-phenyl-1-butylammonium; 1,3-dimethylbutylammonium; 3,3-dimethylbutylammonium; 1-heptylammonium; 1-octylammonium; 1-nonylammonium; 1-decylammonium; 1-eicosylammonium; or any of the foregoing or described herein) may be added. Figure 17-28The bulk organic salt may include any of the foregoing cations, halides, nitrates, nitrites, carboxylates, acetates, acetonyl acetonates, formates, oxalates, sulfates, sulfites, thiosulfates, phosphates, tetrafluoroborate, hexafluorophosphate, tetrakis(perfluorophenyl)borate, hydrides, oxides, peroxides, hydroxides, nitrides, arsenates, arsenites, perchlorates, carbonates, bicarbonates, chromates, dichromates, iodates, bromates, chlorates, chlorites, hypochlorites, hypobromites, cyanides, cyanates, isocyanates, fulminates, thiocyanates, isothiocyanates, azides, tetracarbonylcobaltates, carbamoyl dicyanomethanes, dicyanonitrosomethanides, dicyanamides, tricyanomethanes, amides and / or permanganates. The large volume organic cation salt solution can be formed by dissolving the large volume organic cation salt in a solvent, such as alcohol, anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide (DMF), dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and combinations thereof. In a specific embodiment, the large volume organic cation salt can be dissolved in isopropanol. In certain embodiments, the large volume organic cation salt solution can have the large volume organic cation salt of a concentration of 0.0001M to 1.0M. In other embodiments, the large volume organic cation salt solution can have the large volume organic cation salt of a concentration of 0.01M to 0.1M. In a specific embodiment, the large volume organic cation salt solution can have the large volume organic cation salt of a concentration of 0.02 to 0.05M. In a particular embodiment, the bulk organic cation salt solution can have a bulk organic cation salt at a concentration of 0.05M. The bulk organic cation salt solution can be deposited onto the perovskite material precursor film by any method described herein for solution deposition. These methods can include spraying, dripping, spin coating, slit printing, screen printing, gravure printing or inkjet printing. In one embodiment, the bulk organic cation salt can be 1-butylammonium iodide. In another embodiment, the bulk organic cation salt can be benzyl ammonium iodide. In yet another embodiment, the bulk organic cation salt can be phenylethylammonium iodide.
[0250] The film can then be thermally annealed at a temperature of about 20°C to about 300°C for a period of up to about 24 hours. In one embodiment, the film can be thermally annealed at a temperature of about 50°C for about ten minutes. The perovskite material active layer can then be completed by a conversion process in which the precursor film is immersed or rinsed with a solution comprising a solvent or a solvent mixture (e.g., DMF, isopropanol, methanol, ethanol, butanol, chloroform, chlorobenzene, dimethyl sulfoxide, water) and a salt (e.g., methylammonium iodide, formamidinium iodide, guanidinium iodide, 1,2,2-triaminovinylammonium iodide, 5-aminopentanoic acid hydroiodide) at a concentration of 0.001M to 10M. In certain embodiments, the perovskite material film can also be post-thermally annealed in the same manner as in the first line of this paragraph.
[0251] After the film is deposited and annealed in some embodiments, a second salt precursor (e.g., formamidinium iodide, formamidinium thiocyanate, or guanidinium thiocyanate) can be deposited onto the lead salt film, wherein the film can have a temperature approximately equal to ambient temperature or a controlled temperature of 0°C to 500°C. The second salt precursor can be deposited at ambient temperature or at an elevated temperature between about 25°C and 125°C. The second salt precursor can be deposited by various methods known in the art, including but not limited to spin coating, slit printing, inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, thermal evaporation, or spraying. In some embodiments, multiple subsequent depositions of a second salt solution can be performed to form a thin film layer. In some embodiments, the second salt precursor can be a solution containing one or more solvents. For example, the second salt precursor can contain one or more of anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform and combinations thereof.
[0252] In some embodiments, any bulk organic cation salt described herein can be mixed with the second salt solution before depositing the second salt solution. In a specific embodiment, a bulk organic cation salt solution can be prepared as described above and mixed with the second salt solution before depositing the second salt solution. For example, the bulk organic cation salt solution can have a concentration of 0.0001M to 1.0M of the bulk organic cation salt. In other embodiments, the bulk organic cation salt solution can have a concentration of 0.01M to 0.1M of the bulk organic cation salt. In a specific embodiment, the bulk organic cation salt solution can have a bulk organic cation salt of 0.02 to 0.05M. In a specific embodiment, the bulk organic cation salt solution can have a concentration of about 0.05M of the bulk organic cation salt. In other embodiments, the bulk organic cation salt solution can be deposited onto the lead halide film formed after depositing the lead halide precursor ink or the thin film precursor ink. In another embodiment, the bulk organic cation salt solution can be deposited onto the perovskite precursor film after depositing the second salt solution.
[0253] Finally, the substrate with the perovskite material precursor film can be annealed. Annealing the substrate can convert the lead salt precursor and the second salt precursor into a perovskite material (e.g., FAPbI3, GAPb(SCN)3, FASnI3) having a surface passivation layer of the bulky organic cation. Annealing can be performed in a variety of atmospheres at ambient pressure (e.g., about one atmosphere (760 Torr), depending on altitude and atmospheric conditions) or at a pressure less than atmospheric pressure or ambient pressure (e.g., 1 mTorr to 500 mTorr). The annealing atmosphere can include ambient air, a controlled humidity environment (e.g., 0-100 g H2O / m 3 Gas), pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination of the foregoing gases. The controlled humidity environment may include an environment in which the absolute humidity or % relative humidity is maintained at a fixed value, or in which the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In certain embodiments, the annealing may be performed in a controlled humidity environment in which the % relative humidity is greater than or equal to 0% and less than or equal to 50%. In other embodiments, the annealing may be performed in a controlled humidity environment containing greater than or equal to 0 gH2O / m 3 Gas and less than or equal to 20g H2O / m 3 In some embodiments, the annealing may be performed at a temperature greater than or equal to 50° C. and less than or equal to 300° C.
[0254] For example, in one particular embodiment, the FAPbI3 perovskite material can be formed by the following process. First, a lead (II) halide precursor comprising about 90:10 molar ratio of PbI2 and PbCl2 dissolved in anhydrous DMF is deposited onto a substrate by spin coating, doctor blading, or slot printing. In a substantially anhydrous atmosphere (i.e., less than 30% relative humidity or 17 g H2O / m 3 ) in a 50% molten metal film and dried for about one hour (± 15 minutes) to form a film. The film can be subsequently thermally annealed for about 10 minutes at a temperature of about 50° C. (± 10° C.). In other embodiments, the lead halide precursor can be deposited by inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation or spraying. Then, a 1-butylammonium salt solution having a concentration of 0.05M in isopropanol can be deposited on the lead halide film. Then, a formamidinium iodide precursor containing 15-100mg / mL of formamidinium iodide (dissolved in anhydrous isopropanol) can be deposited on the lead halide film by spin coating or blade coating. In other embodiments, the formamidinium iodide precursor can be deposited by inkjet printing, gravure printing, screen printing, slit printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation or spraying. Next, the substrate can be heated at about 25% relative humidity (about 4 to 7 g H2O / m 3 Gas) and annealed at about 100° C. to 200° C. to form a formamidinium lead iodide (FAPbI3) perovskite material with a surface layer of 1-butylammonium. In an alternative embodiment, the 1-butylammonium salt solution can be deposited on a film formed after depositing the formamidinium iodide precursor. In another embodiment, the 1-butylammonium salt solution can be combined with the lead halide precursor ink before depositing the lead halide precursor ink. In yet another embodiment, the 1-butylammonium salt solution can be combined with the formamidinium iodide precursor before depositing the formamidinium iodide precursor. In yet another embodiment, the 1-butylammonium salt solution can be deposited on the film after depositing the formamidinium iodide precursor and before annealing the film with a substrate. In yet another embodiment, the 1-butylammonium salt solution can be deposited on the film after annealing the film with a substrate.
[0255] In other embodiments, the above method can be used to obtain a lead (II) iodide solution, a cesium iodide solution, a methylammonium (MA) iodide salt solution and a 1-butylammonium salt solution to obtain a compound having the formula Cs i A perovskite material of MAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is 1-butylammonium. As another example, a lead (II) iodide solution, a rubidium iodide solution, a formamidinium iodide (FA) salt solution, and a 1-butylammonium salt solution can be used to obtain a perovskite material having the formula Rb iA perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is a 1-butylammonium layer. As another example, a lead (II) iodide solution, a cesium iodide solution, a formamidinium iodide (FA) salt solution, and a 1-butylammonium salt solution can be used to obtain a perovskite material having the formula Cs i A perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is a 1-butylammonium layer. As another example, a lead (II) iodide solution, a potassium iodide solution, a formamidinium iodide (FA) salt solution, and a 1-butylammonium salt solution can be used to obtain a perovskite material having the formula K i A perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is a 1-butylammonium layer. As another example, a lead (II) iodide solution, a sodium iodide solution, a formamidinium iodide (FA) salt solution, and a 1-butylammonium salt solution can be used to obtain a perovskite material having the formula Na i A perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is a 1-butylammonium layer. As another example, a lead (II) iodide-lead (II) chloride mixture solution, a cesium iodide solution, a formamidinium iodide (FA) salt solution, and a 1-butylammonium salt solution can be used to obtain a perovskite material having the formula Cs i FqV 3-y Cl y A perovskite material wherein i is equal to a number from 0 to 1, and y represents a number from 0 to 3, and the surface layer is a 1-butylammonium layer.
[0256] In another embodiment, the FAPbI3 perovskite material can be formed by the following process. First, a lead (II) halide precursor comprising about 90:10 molar ratio of PbI2 and PbCl2 dissolved in anhydrous DMF is deposited onto a substrate by spin coating, blade coating, or slot printing. In a substantially anhydrous atmosphere (i.e., less than 30% relative humidity or 17 g H2O / m 3) in a 50% mol / l film to form a lead halide precursor ink. The film can be subsequently thermally annealed at a temperature of about 50° C. (±10° C.) for about 10 minutes. In other embodiments, the lead halide precursor can be deposited by inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation or spraying. Then, a formamidinium iodide precursor containing 15-60 mg / mL of formamidinium iodide (dissolved in anhydrous isopropanol) can be deposited on the lead halide film by spin coating or blade coating. In other embodiments, the formamidinium iodide precursor can be deposited by inkjet printing, gravure printing, screen printing, slit printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation or spraying. After the lead halide precursor and the formamidinium iodide precursor are deposited, a 0.04 M solution of benzyl ammonium salt in isopropanol may be deposited onto the perovskite material precursor film. The substrate may then be heated at about 25% relative humidity (about 4 to 7 g H2O / m 3 Gas) and annealed at about 100° C. to 200° C. to form a formamidinium lead iodide (FAPbI3) perovskite material having a surface layer of benzyl ammonium. In a particular embodiment, a benzyl ammonium salt solution may be deposited on a lead halide film before depositing the formamidinium iodide precursor. In another embodiment, a benzyl ammonium salt solution may be combined with the lead halide precursor ink before depositing the lead halide precursor ink. In yet another embodiment, a benzyl ammonium salt solution may be combined with the formamidinium iodide precursor before depositing the formamidinium iodide precursor. In some embodiments, the resulting perovskite material may have a cubic crystal structure in the bulk material away from the surface. The presence of bulky organic cations near the surface of the perovskite material may result in a non-cubic crystal structure near the surface of the perovskite material.
[0257] In other embodiments, the above method can be used to obtain a lead (II) iodide solution, a cesium iodide solution, a methylammonium (MA) iodide salt solution and a 1-butylammonium salt solution to obtain a compound having the formula Cs i A perovskite material of MAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is benzyl ammonium. As another example, a lead (II) iodide solution, a rubidium iodide solution, a formamidinium iodide (FA) salt solution, and a benzyl ammonium salt solution can be used to obtain a perovskite material having the formula Rb i A perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is a benzyl ammonium layer. As another example, a lead (II) iodide solution, a cesium iodide solution, a formamidinium iodide (FA) salt solution, and a benzyl ammonium salt solution can be used to obtain a perovskite material having the formula Cs i A perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is a benzyl ammonium layer. As another example, a lead (II) iodide solution, a potassium iodide solution, a formamidinium iodide (FA) salt solution, and a benzyl ammonium salt solution can be used to obtain a perovskite material having the formula Ki A perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is a benzyl ammonium layer. As another example, a lead (II) iodide solution, a sodium iodide solution, a formamidinium iodide (FA) salt solution, and a benzyl ammonium salt solution can be used to obtain a perovskite material having the formula Na i A perovskite material of FAPbI3, wherein i is equal to a number from 0 to 1, and the surface layer is a benzyl ammonium layer. As another example, a lead (II) iodide-lead (II) chloride mixture solution, a cesium iodide solution, a formamidinium iodide (FA) salt solution, and a benzyl ammonium salt solution can be used to obtain a perovskite material having the formula Cs i FqV 3-y Cl y A perovskite material, wherein i is equal to a number from 0 to 1, and y represents a number from 0 to 3, and the surface layer is a benzyl ammonium layer.
[0258] The method for manufacturing a perovskite material with benzyl ammonium is described below. First, a lead iodide precursor ink is prepared by dissolving PbI2, PbCl2 and cesium iodide (CsI) in a mixture of DMF and DMSO solvent. In order to prepare the lead iodide precursor ink, a 1.5M CsI / DMSO solution is prepared by dissolving CsI in DMSO. In a specific embodiment, the CsI / DMSO solution can be prepared by stirring CsI into DMSO at a ratio of 1.5mmol of CsI per 1.0mL of anhydrous DMSO for 1 to 2.5 hours at room temperature. Then, the aforementioned CsI solution is added to a solution of PbI2, PbCl2 and anhydrous DMF solvent to form a 1.28M Pb 2+ A 1.28 M Pb solution can be prepared by adding a CsI solution to a container containing 1.26 mmol PbI2, 0.14 mmol PbCl2, and 1.0 mL anhydrous DMF solvent for every 93.8 μL of CsI solution. 2+ Solution. The Pb 2+ The solution is mixed at a temperature of 50°C to 100°C for 1.5 to 2.5 hours and then cooled to form a lead iodide precursor ink. In a specific embodiment, the Pb 2+ The solution may be stirred at 85°C for two hours and then cooled by stirring the solution at room temperature for one hour. In some embodiments, the lead iodide precursor ink may be filtered prior to depositing the lead iodide precursor ink. In a particular embodiment, a 0.2 μm filter may be used to filter the lead iodide precursor ink.
[0259] Formamidinium iodide (FAI) and benzyl ammonium iodide (BzAI) solutions were prepared by dissolving FAI and BzAI salts in anhydrous isopropyl alcohol (IPA) to form 0.2 M FAI solution and 0.05 M BzAI solution, respectively. In certain embodiments, both FAI and BzAI solutions can be maintained at 75°C during subsequent coating processes.
[0260] Next, the lead iodide precursor ink is deposited onto the substrate and then annealed to form a lead iodide film. In a specific embodiment, the lead iodide precursor ink maintained at 45°C can be blade coated onto a substrate coated with a nickel oxide (NiO) thin film layer and then annealed at 50°C for 10 minutes to form a lead iodide film.
[0261] Next, to form a perovskite material layer, the lead iodide film is first rinsed with a single coating of a BzAI solution and then three coatings of a FAI solution. After each coating of the BzAI solution and the FAI solution is deposited, the coating is dried before the next coating is deposited. In a specific embodiment, the BzAI and FAI solutions may be maintained at 45°C during the deposition of each respective coating. After depositing the third FAI coating, the substrate and coating may be annealed to form a perovskite material layer. In a specific embodiment, immediately after depositing the third FAI, the substrate is heated to 157°C for 5 minutes to anneal the perovskite material layer.
[0262] The foregoing method can have multiple advantages. For example, depositing the BzAI solution onto the lead iodide film before depositing the FAI solution can provide an intermediate template for the growth of the 3DFAPbI3 perovskite material by forming a 2D perovskite material. The BzAI can react with the lead iodide film to form an intermediate 2D perovskite material phase. When reacting with FAI after the FAI solution is deposited, the BzAI in the 2D phase + The cation can be completely or partially replaced by FA + The cations are replaced to form a 3D FAPbI3 framework. In addition, BzAI can also passivate crystal defects in 3D FAPbI3 perovskite materials. Compared with the FAbI3 film formed by the method that does not include BzAI, the photoluminescence intensity of the FAPbI3 film formed by the above method is brighter (higher). Fig.31 Optical (absorbance) and photoluminescence images of a perovskite material photovoltaic device 3105 made without the addition of BzAI and a perovskite material photovoltaic device 3110 made with BzAI as described herein are shown. Fig.31It is shown that the optical image of the perovskite material photovoltaic device 3110 is darker, showing a higher absorbance, and the photoluminescence image of the perovskite material photovoltaic device 3110 is brighter than the perovskite material photovoltaic device 3105. In addition, greater power output from the perovskite material photovoltaic device incorporating BzAI has been observed. Fig.32 A power output curve 3205 corresponding to a photovoltaic device without BzAI (such as photovoltaic device 3105) and a power output curve 3210 corresponding to a photovoltaic device with BzAI as described herein (such as photovoltaic device 3110) are shown. 2 Measured at maximum power point under AM1.5G illumination for 180 seconds (30 seconds of dark measurement inserted in the middle to demonstrate steady-state performance) Fig.32 The power output measurements depicted in . Fig.32 It can be seen that compared with the photovoltaic device made without BzAI (15.0 mW / cm 2 , 770mV and 19.5mA / cm 2 ) compared to PV devices that incorporate BzAI during production, which produces more power per unit area (16.0 mW / cm 2 ), higher voltage (785mV), and more current per unit area (20.3mA / cm 2 ). Fig.33 The current-voltage (IV) scan 3320 of a perovskite material photovoltaic device made without BzAI (labeled as sample "5r" line) and a perovskite material photovoltaic device made with BzAI (labeled as sample "10r" line) is shown. Fig.33 It can be seen that the perovskite photovoltaic device made with BzAI produces a larger current across a certain bias range of voltages than the perovskite photovoltaic device made without BzAI. In addition, Fig.34 Box plots of open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF), and power conversion efficiency (PCE) are shown for six perovskite material photovoltaic devices made without BzAI (sample 5, r = reverse scan, f = forward scan, and s = steady-state measurement) and six perovskite material photovoltaic devices made with BzAI (sample 10). Fig.35 The external quantum efficiency (EQE) of six perovskite material photovoltaic devices made without BzAI (curve 3505) and six perovskite material photovoltaic devices made with BzAI (curve 3510) are shown. Fig.35 Each EQE curve has been integrated to estimate the 2The Jsc in units of , indicates that the perovskite material device made with BzAI exhibits a higher Jsc (area under the EQE curve) than the perovskite material device made without BzAI. Fig.36 Admittance spectra 3605 of a perovskite material photovoltaic device made without BzAI and admittance spectra 3610 of a perovskite material photovoltaic device made with BzAI are shown. Admittance spectra 3610 shows the suppressed ion migration of the sample device including benzyl ammonium when compared to the admittance spectra 3605 of the sample device not including benzyl ammonium. Excessive ion migration is known to have a detrimental effect on the performance and durability of perovskite material devices, indicating that the inclusion of benzyl ammonium in perovskite material photovoltaic devices can improve device performance and durability.
[0263] Perovskite enhanced by diammonium butane cation
[0264] Incorporating 1,4-diammoniumbutane or other polyammonium organic compounds as described below into the crystal structure of the perovskite material can improve the properties of the material. In one embodiment, adding 1,4-diammoniumbutane to FAPbI3 perovskite as described below can provide a perovskite material with favorable properties. In some embodiments, 1,4-diammoniumbutane salts can be used to replace the bulky organic cation salts in the above method to incorporate 1,4-diammoniumbutane into the perovskite material, and the addition of 1,4-diammoniumbutane salts (or other organic polyammonium salts described herein) can be performed at any stage of the perovskite production method (for which the addition of bulky organic cations is described above). Including organic cations such as 1,4-diammoniumbutane into the crystal structure of the perovskite material can cause the chemical formula of the perovskite material to deviate from the "ideal" stoichiometric ratio of the perovskite material disclosed herein. For example, the inclusion of such organic cations can cause the perovskite material to have a substoichiometric or superstoichiometric chemical formula relative to the FAPbI3 chemical formula. In this case, the general formula of the perovskite material can be expressed as C x M y X z , where x, y, and z are real numbers.
[0265] In one embodiment, a 1,4-diammonium butane salt solution may be added to the lead halide precursor ink solution prior to deposition. In certain embodiments, the 1,4-diammonium butane salt may be added to the lead halide precursor ink solution at a concentration of 0.001 mol % to 50 mol %. In some embodiments, the 1,4-diammonium butane salt may be added to the lead halide precursor ink solution at a concentration of 0.1 mol % to 20 mol %. In a specific embodiment, the 1,4-diammonium butane salt may be added to the lead halide precursor ink solution at a concentration of 1 mol % to 10 mol %.
[0266] In another embodiment, 1,4-diammonium butane salt can be added to the formamidinium salt solution before contacting the formamidinium salt solution with the lead halide precursor film as described above. In certain embodiments, 1,4-diammonium butane salt can be added to the formamidinium iodide salt solution at a concentration of 0.001 mol % to 50 mol %. In some embodiments, 1,4-diammonium butane salt can be added to the formamidinium iodide salt solution at a concentration of 0.1 mol % to 20 mol %. In a specific embodiment, 1,4-diammonium butane salt can be added to the formamidinium iodide salt solution at a concentration of 1 mol % to 10 mol %.
[0267] In other embodiments, the 1,4-diammonium butane salt precursor solution can be deposited onto a lead halide film formed after the lead halide precursor ink is deposited or onto a perovskite precursor film after the formamidinium salt solution is deposited. In certain embodiments, the 1,4-diammonium butane salt precursor solution can have a concentration of 0.001 mol % to 50 mol %. In some embodiments, the 1,4-diammonium butane salt precursor solution can have a concentration of 0.1 mol % to 20 mol %. In a specific embodiment, the 1,4-diammonium butane salt precursor solution can have a concentration of 1 mol % to 10 mol %.
[0268] An exemplary method of depositing a perovskite material including 1,4-diammoniumbutane includes depositing a lead salt precursor onto a substrate to form a lead salt film, and depositing an organic cation salt precursor comprising a first organic cation salt onto the lead salt film to form a perovskite precursor film. The lead salt precursor or the organic cation salt precursor may include a 1,4-diammoniumbutane salt, or the 1,4-diammoniumbutane salt precursor may be deposited onto the lead salt film or the perovskite precursor film. Finally, the substrate and the perovskite precursor film may be annealed to form a perovskite material including 1,4-diammoniumbutane. The lead salt precursor and the organic cation salt precursor may include any solution described herein for preparing a perovskite film.
[0269] The length between the ammonium groups of 1,4-diammonium butane is almost the same as the length between the methylamidinium cations in the lattice of the methylamidinium lead iodide perovskite material. Therefore, in the process of forming the FAPbI3 material, 1,4-diammonium butane can replace two methylamidinium ions. In an alternative embodiment, other alkyl polyammonium salts can be added to the lead halide precursor ink in the process of forming the perovskite material. For example, 1,8-diammonium octane, bis(4-aminobutyl)amine and tris(4-aminobutyl)amine can be added. In addition, polyammonium polycations (including 1,4-diammonium butane) can provide the same benefits as the above-mentioned bulky organic cations through a mechanism similar to that described above for bulky organic cations.
[0270] Fig.13This is a stylized illustration of the effect of adding 1,4-butanediammonium salt to the resulting perovskite 7000 during the process of making the perovskite material. Fig.13 As shown, the 1,4-diammoniumbutane cation 7020 can replace two formamidinium cations 7010 in the perovskite material lattice. In the FAPbI3 perovskite, the spacing between the formamidinium cations is about The length of the 1,4-diammoniumbutane cation is approximately The difference is only Therefore, 1,4-diammonium butane cations can be substituted into the perovskite lattice without significantly changing the properties or structure of the perovskite lattice. In some embodiments, adding 1,4-diammonium butane cations to the perovskite material can enhance the properties and stability of the perovskite material. 1,4-diammonium butane cations can act as a rigid structure in the perovskite material, improving its structural and chemical durability. For example, in some embodiments, compared with the perovskite material without 1,4-diammonium butane cations, the perovskite material with added 1,4-diammonium butane cations can exhibit excellent dry heat stability. In addition, the perovskite material with added 1,4-diammonium butane cations can show a blue shift in the emission spectrum of the perovskite material. In some embodiments, 1,4-diammonium butane cations can be added to the guanidine salt solution at a concentration of 0 to 20 mol%. In other embodiments, 1,4-diammonium butane cations can be added to the guanidine salt solution at a concentration of 1 to 5 mol%. In a particular embodiment, the 1,4-diammoniumbutane cation is added to the formamidinium salt solution at a concentration of 5 mol%.
[0271] Experimental evidence shows that there is no noticeable change in the lattice parameters for the addition of up to 20% 1,4-diammoniumbutane to the perovskite material. Fig.14 X-ray diffraction peaks (XRD) of perovskites with 0 mol%, 5 mol%, 10 mol% and 20 mol% of 1,4-diammoniumbutane ("DABI") are provided. For each concentration, the main peak appears at the same point, indicating that the lattice parameters of the perovskite material do not change significantly when 1,4-diammoniumbutane is added at concentrations of 0 mol% to 20 mol%. The addition of 1,4-diammoniumbutane can produce a small intensity diffraction at less than 13° 2θ with Cu-Kα radiation, which indicates a small amount of 2D or layered perovskite phase.
[0272] Fig.15Images of perovskite samples with 0 mol%, 1 mol%, 2.5 mol%, and 5 mol% exposed to a temperature of 85°C and a relative humidity of 0% for seven days are provided. The perovskite material containing 0 mol% DABI shows a significant lightening of color after one day, and an even more significant yellowing after seven days. This indicates that the perovskite material with 0 mol% DABI has been significantly degraded after one day of exposure to the test conditions. The perovskite material samples with 1 mol%, 2.5 mol%, and 5 mol% all remain dark after seven days, indicating that the addition of as little as 1 mol% DABI also significantly improves the so-called "dry heat" stability of the perovskite material.
[0273] Furthermore, the addition of 1,4-diammoniumbutane to the perovskite material can result in a slight blue shift in the photoluminescence observed from the perovskite material when compared to a perovskite material without 1,4-diammoniumbutane. This blue shift is due to the passivation of trap states in the perovskite material due to the addition of 1,4-diammoniumbutane. The blue shift indicates that the addition of 1,4-diammoniumbutane to the perovskite material reduces the defect density in the lattice of the perovskite material without changing the crystal structure of the perovskite material. For example, it has been observed that the resulting blue shift observed in the FAPbI3 perovskite material with 20 mol% of added 1,4-diammoniumbutane is a change of 0.014 eV, from 1.538 eV without 1,4-diammoniumbutane to 1.552 eV with 20 mol% 1,4-diammoniumbutane, compared to the FAPbI3 perovskite material without 1,4-diammoniumbutane.
[0274] In other embodiments, other ammonium complexes may be added during the formation of the perovskite material. For example, Fig.16 Three ammonium compounds are shown, 1,8-diammonium octane, bis(4-aminobutyl)-ammonium and tris(4-aminobutyl)-ammonium, which can be added to the perovskite material in the same manner as described above for 1,4-diammonium butane cations. When introduced in the process of forming the perovskite material as described above, 1,8-diammonium octane can occupy the space of two guanidine cations ("A sites") of the FAPbI3 perovskite material lattice. When introduced in the process of forming the perovskite material as described above, bis(4-aminobutyl)-ammonium can occupy the space of three A sites of the FAPbI3 perovskite material lattice. When introduced in the process of forming the perovskite material as described above, tris(4-aminobutyl)-ammonium can occupy the space of four A sites of the FAPbI3 perovskite material lattice. Fig.16A -C provides Fig.16 A stylized illustration of the incorporation of the three ammonium compounds shown in Figure 1 into the crystal lattice of the FAPbI3 perovskite material. Fig.16A is a stylized illustration of the incorporation of 1,8-diaminoctane into the FAPbI3 perovskite material lattice 7100. Fig.16AAs shown, the 1,8-diammonium octanium cation 7120 can replace two formamidinium cations 7110 in the perovskite material lattice. Fig. 16B is a stylized illustration of the incorporation of bis(4-aminobutyl)-ammonium into the FAPbI3 perovskite material lattice 7200. Fig. 16B As shown, the bis(4-aminobutyl)-ammonium cation 7220 can replace three formamidinium cations 7210 in the perovskite material lattice. Fig. 16C is a stylized illustration of the incorporation of tris(4-aminobutyl)-ammonium into the FAPbI3 perovskite material lattice 7300. Fig.16 c, the tri(4-aminobutyl)-ammonium cation 7320 can replace four carboxamidinium cations 7310 in the perovskite material lattice. In other embodiments, an alkyl diammonium complex having a carbon chain of 2 to 20 carbon atoms can be added to the perovskite material. In some embodiments, a combination of ammonium complexes can be added to the perovskite material.
[0275] Therefore, the present invention is well suited to obtain the objects and advantages mentioned and the objects and advantages inherent therein. The specific embodiments disclosed above are merely illustrative, as the present invention can be modified and implemented in different but equivalent ways apparent to those skilled in the art who benefit from the teachings herein. Further, except as described in the claims below, it is not intended to limit the details of the structure or design shown herein. It is therefore apparent that the specific illustrative embodiments disclosed above can be changed or modified, and all such changes are considered to be within the scope and spirit of the present invention. Specifically, the form of each numerical range disclosed herein ("from about a to about b", or equivalently "from about a to b", or equivalently "about ab") should be understood to refer to the power set (the set of all subsets) of the corresponding numerical range, and to list each range covered in a wider numerical range. Moreover, unless otherwise clearly and clearly defined by the patentee, the terms in the claims have their ordinary and original meanings.
Claims
1. Perovskite materials, including: With formula C x M y X z The perovskite lattice; and Alkyl polyammonium cations located within or on the surface of the perovskite lattice; in: x, y and z are real numbers; C comprises one or more cations selected from the group consisting of Group 1 metals, Group 2 metals, ammonium, formamidinium, guanidinium, and ethylenetetramine; M comprises one or more metals, each of which is selected from Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr, and combinations thereof; and X comprises one or more anions, each of which is selected from the group consisting of halides, pseudohalides, chalcogenides, and combinations thereof.
2. The perovskite material of claim 1, wherein the alkyl polyammonium cation is selected from butane-1,4-diammonium, 1,8-diammonium octane, bis(4-aminobutyl)-ammonium or tris(4-aminobutyl)-ammonium.
3. The perovskite material of claim 1, wherein the alkyl polyammonium cation has a concentration of 1 mol% to 20 mol% in the perovskite material.
4. The perovskite material of claim 1, wherein the alkyl polyammonium cation has a concentration of 1 mol% to 5 mol% in the perovskite material.
5. The perovskite material of claim 1, wherein the alkyl polyammonium cation has a concentration of about 5 mol% in the perovskite material.
6. The perovskite material of claim 1, wherein C comprises formamidinium, M comprises lead, and X comprises iodide.
7. The perovskite material of claim 1, wherein the perovskite material lattice has a cubic structure.
8. The perovskite material of claim 1, wherein the ammonium group of the alkyl polyammonium cation replaces the formamidinium ion in the perovskite lattice.
9. Perovskite materials, including: Formamidinium lead iodide perovskite materials; and Alkyl polyammonium cations dispersed in or on the surface of formamidinium lead iodide perovskite materials.
10. The perovskite material of claim 9, wherein the alkyl polyammonium cation comprises butane-1,4-diammonium, 1,8-diammonium octane, bis(4-aminobutyl)-ammonium, or tris(4-aminobutyl)-ammonium.
11. The perovskite material of claim 9, wherein the ammonium group of the alkyl polyammonium cation replaces the formamidinium ion in the formamidinium lead iodide perovskite material.
12. The perovskite material of claim 9, wherein the alkyl polyammonium cation has a concentration of 1 mol% to 20 mol% in the perovskite material.
13. The perovskite material of claim 9, wherein the alkyl polyammonium cation has a concentration of 1 mol% to 5 mol% in the perovskite material.
14. The perovskite material of claim 9, wherein the alkyl polyammonium cation has a concentration of about 5 mol% in the perovskite material.
15. The perovskite material of claim 9, wherein the formamidinium lead iodide perovskite material has a cubic crystal structure.
16. Methods for depositing perovskite materials, include: depositing a lead salt precursor onto a substrate to form a lead salt thin film, wherein the lead salt precursor comprises a lead salt or an alkyl polyammonium salt; depositing a second salt precursor onto the lead salt film to form a perovskite precursor film; and The substrate and the perovskite precursor film are annealed to form a perovskite material.
17. The perovskite material of claim 16, wherein the alkyl polyammonium cation comprises butane-1,4-diammonium, 1,8-diammonium octane, bis(4-aminobutyl)-ammonium, or tris(4-aminobutyl)-ammonium.
18. The perovskite material of claim 16, wherein the lead salt precursor has an alkyl polyamine salt concentration of 1 mol% to 20 mol%.
19. The method of claim 16, wherein the lead salt is selected from the group consisting of lead (II) iodide, lead (II) thiocyanate, lead (II) chloride, lead (II) bromide, and combinations thereof.
20. The method of claim 16, wherein the lead salt comprises lead (II) iodide.
21. The method of claim 16, wherein the second salt precursor comprises a salt selected from the group consisting of formamidinium iodide, formamidinium thiocyanate, guanidinium thiocyanate, and combinations thereof.
22. The method of claim 16, wherein the second salt precursor comprises formamidinium iodide.
23. The method of claim 16, wherein the lead salt precursor comprises one or more additives selected from the group consisting of amino acids, 5-aminopentanoic acid hydroiodide, 1,8-diiodooctane, 1,8-dithiooctane, formamidinium halides, acetic acid, trifluoroacetic acid, methylammonium halides, water, and combinations thereof.
24. The method of claim 16, wherein the lead salt precursor comprises a 90:10 molar ratio of PbI dissolved in anhydrous dimethylformamide. 2 With PbCl 2 .
25. The method of claim 16, wherein the annealing is performed at a temperature greater than or equal to 50°C and less than or equal to 300°C.
26. The method of claim 16, wherein the annealing is performed at a temperature greater than or equal to 0 g H 2 O / m 3 Air and less than or equal to 20g H 2 O / m 3 The absolute humidity of the air.
27. The method of claim 27, wherein the annealing is performed at about 4 to 7 g H 2 O / m 3 The absolute humidity of the air.
28. Methods for depositing perovskite materials, include: depositing a lead salt precursor onto a substrate to form a lead salt thin film; Predepositing an alkyl polyamine salt on the lead salt film; depositing a third salt precursor onto the lead salt film to form a perovskite precursor film; and The substrate and the perovskite precursor film are annealed to form a perovskite material.
29. The method of claim 28, in: The lead salt precursor comprises lead (II) iodide; The third salt precursor comprises formamidinium iodide.
30. The method of claim 28, in: The lead salt precursor consisted of a 90:10 molar ratio of PbI dissolved in anhydrous dimethylformamide. 2 With PbCl 2 ; The lead salt precursor contains up to 10 mol % cesium; and Annealing is performed at a temperature of 50°C or more and 300°C or less.
